Method for producing sulfide solid electrolyte

By mixing the raw materials of lithium, phosphorus, sulfur and halogen with complexing agent in the liquid phase method and removing the complexing agent in the heated gas stream, the sulfide solid electrolyte has low conductivity and poor mass production in the prior art. Problem, efficient and high-quality electrolyte preparation has been achieved.

CN119497896APending Publication Date: 2025-02-21IDEMITSU KOSAN CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380052014.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-13
Filing Date
2023-07-10
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

It is difficult to efficiently manufacture sulfide solid electrolytes with high ionic conductivity in the prior art. Especially in the liquid phase method, there are problems of solvent residue and low efficiency in removal of complexing agents, which affects the quality and mass production of the electrolyte.

Method used

By mixing raw materials containing lithium, phosphorus, sulfur and halogen with a complexing agent, an electrolyte precursor is formed and heated in a heating gas stream, thereby removing the complexing agent and achieving efficient preparation of the electrolyte.

Benefits of technology

This method can efficiently remove complexing agent, reduce solvent residue, improve the ionic conductivity and quality of sulfide solid electrolytes, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497896A_ABST
    Figure CN119497896A_ABST
Patent Text Reader

Abstract

Provided is a method for easily and efficiently producing or mass-producing a sulfide solid electrolyte having high ionic conductivity using a liquid phase method, the method comprising: mixing a complexing agent and a starting material containing a lithium atom, a phosphorus atom, a sulfur atom, and a halogen atom; obtaining an electrolyte precursor-containing substance containing a powder of an electrolyte precursor; and then heating is carried out in a heating air flow.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a sulfide solid electrolyte. Background Art

[0002] In recent years, with the rapid popularization of information-related devices or communication devices such as personal computers, cameras and mobile phones, the development of batteries used as their power sources has also received attention. In the past, in batteries used for such purposes, electrolytes containing flammable organic solvents were used, but by making the battery fully solid, the safety device is simplified because no flammable organic solvent is used in the battery, and the manufacturing cost and productivity are excellent. Therefore, the development of batteries in which the electrolyte is replaced by a solid electrolyte layer is carried out.

[0003] The manufacturing method of the solid electrolyte used for the solid electrolyte layer is roughly divided into a solid phase method and a liquid phase method, and the liquid phase method includes a uniform method in which the solid electrolyte material is completely dissolved in a solvent, and an inhomogeneous method in which the solid electrolyte material is not completely dissolved but a suspension is coexistent with solid and liquid. For example, as a uniform method in the liquid phase method, a method of dissolving a solid electrolyte in a solvent and reprecipitating it is known (for example, see Patent Document 1), and as an inhomogeneous method, a method of reacting a solid electrolyte raw material such as lithium sulfide in a solvent containing a polar aprotic solvent is known (for example, see Patent Documents 2 and 3, Non-Patent Document 1).

[0004] Furthermore, there are also known methods for producing a solid electrolyte comprising using a specific compound having an amino group as a complexing agent and mixing the complexing agent with a solid electrolyte raw material to prepare an electrolyte precursor (for example, see Patent Document 4), and methods for producing a solid electrolyte comprising drying a slurry containing a complexing agent and an electrolyte precursor by fluidized drying using dielectric particles (for example, see Patent Document 5).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-191899

[0008] Patent Document 2: International Publication No. 2014 / 192309

[0009] Patent Document 3: International Publication No. 2018 / 054709

[0010] Patent Document 4: International Publication No. 2020 / 105737

[0011] Patent Document 5: International Publication No. 2021 / 230189

[0012] Non-patent literature

[0013] Non-patent document 1: Chemistry of Materials, 2017, No. 29, pp. 1830-1835 Summary of the invention

[0014] Technical problem to be solved by the invention

[0015] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a method for producing a sulfide solid electrolyte having high ion conductivity easily and efficiently by a liquid phase method or by mass production.

[0016] Solutions for solving the above technical problems

[0017] The method for producing a sulfide solid electrolyte of the present invention comprises:

[0018] Mixing a raw material containing lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms with a complexing agent to obtain an electrolyte precursor containing material; and

[0019] Then heating is carried out in a heated air flow.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide a method for producing or mass-producing a sulfide solid electrolyte having high ion conductivity by a liquid phase method and easily and efficiently. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a flow chart of the device including the airflow dryer and the bag filter used in Example 1.

[0023] Figure 2 This is an X-ray diffraction spectrum of the crystalline sulfide solid electrolyte obtained in Example 3.

[0024] Figure 3 These are X-ray diffraction spectra of the crystalline sulfide solid electrolytes obtained in Examples 3 to 8.

[0025] Figure 4 : These are X-ray diffraction spectra of the crystalline sulfide solid electrolytes obtained in Comparative Examples 1 and 2.

[0026] Figure 5 This is a flow chart of an apparatus including a fluidized bed dryer and a bag filter used in Comparative Example 3.

[0027] Figure 6 These are X-ray diffraction spectra of the crystalline sulfide solid electrolytes obtained in Comparative Example 3 and Examples 3 and 6.

[0028] Figure 7 These are X-ray diffraction spectra of the crystalline sulfide solid electrolytes obtained in Examples 9 to 15. DETAILED DESCRIPTION

[0029] Hereinafter, an embodiment of the present invention (hereinafter sometimes referred to as "the present embodiment") is described. In addition, in this specification, the upper and lower limit values ​​involved in the numerical ranges of "above", "below", and "to" are values ​​that can be arbitrarily combined, and the values ​​of the embodiments can also be used as the upper and lower limit values. In addition, preferred provisions can be adopted arbitrarily. That is, a preferred provision can be combined with another preferred provision or multiple provisions. It can be said that the combination of preferred provisions is more preferred.

[0030] (Discovery made by the present inventors to complete the present invention)

[0031] The present inventors have conducted intensive studies to solve the above-mentioned technical problems and, as a result, have found the following matters and have completed the present invention.

[0032] In recent years, with the goal of practical application of all-solid-state batteries, the liquid phase method has attracted attention as a method that is versatile and applicable and can be synthesized easily and in large quantities.

[0033] The liquid phase method has the advantages as described above, but on the other hand, due to the dissolution of the solid electrolyte, a part of the solid electrolyte components is decomposed and damaged during precipitation, so compared with the solid phase method, there is a problem that it is difficult to achieve high ionic conductivity. For example, in the uniform method, since the raw materials and the solid electrolyte are temporarily completely dissolved, the components can be evenly dispersed in the liquid. However, in the subsequent precipitation process, precipitation is carried out according to the solubility inherent to each component, so it is extremely difficult to precipitate it under the state of maintaining the dispersed state of the component. As a result, each component is separated and precipitated. In addition, in the uniform method, the affinity of the solvent and lithium becomes too strong, so even if it is dried after precipitation, it is not easy to separate the solvent. Therefore, in the uniform method, there is a problem that the ionic conductivity of the solid electrolyte is greatly reduced. In addition, in the inhomogeneous method where solid and liquid coexist, since a part of the solid electrolyte is dissolved, there is also a problem that separation is produced due to the elution of a specific component, and it is difficult to obtain the desired solid electrolyte.

[0034] In addition, regarding the liquid phase method (heterogeneous method), for example, in the method of producing a sulfide solid electrolyte using a complexing agent via an electrolyte precursor described in Patent Document 4, a step of removing the complexing agent is required. The present inventors have focused on a method of removing the complexing agent in the method of producing a sulfide solid electrolyte using a complexing agent via an electrolyte precursor.

[0035] In the manufacturing method described in patent document 4, the removal of the complexing agent is carried out in the following manner: after the electrolyte precursor containing material in the form of a slurry is dried under vacuum and at room temperature to form a powdered electrolyte precursor, the electrolyte precursor is heated at 120°C under vacuum (Example 1, etc.), specifically, a jacketed heater (vibration dryer, etc.) is used under vacuum to remove the complexing agent. In this way, when a complexing agent is used, the complexing agent cannot be removed from the electrolyte precursor only by drying, but a jacketed heater (vibration dryer, etc.) is used for heating. However, in such a heater, even if the complexing agent can be removed, the wall surface inside the heater locally becomes a high temperature, and sometimes the condensation of the halogen compound contained in the solid electrolyte is generated, resulting in the degradation of the solid electrolyte. Therefore, the temperature conditions when removing the complexing agent are limited, and there is room for improvement in efficiently manufacturing solid electrolytes.

[0036] Furthermore, as the demand for sulfide solid electrolytes increases, there is a demand for mass production. However, in the conventional method, since heating is performed under vacuum, the complexing agent is removed in an environment where heat is transferred only by contact between the powder and the inner wall surface (heat transfer surface) of the jacket-type heater, which has a great impact on the large-scale equipment and may not be able to fully cope with it.

[0037] Regarding the removal of the complexing agent, no complexing agent is used in Patent Documents 1 to 3. Furthermore, although it is assumed that a solvent is used during the reaction of the solid electrolyte raw material, there is no research on a method for removing the solvent.

[0038] In the manufacturing method described in Patent Document 5, the slurry containing the complexing agent and the electrolyte precursor is dried by using fluidized drying of the medium particles. However, in the manufacturing method described in Patent Document 5, the operation of removing the complexing agent from the electrolyte precursor is not performed during the drying of the slurry, so the complexing agent is removed from the electrolyte precursor obtained by the drying by heating at 110° C. under vacuum in the same manner as the manufacturing method described in Patent Document 4 (Example 1, etc.), specifically, a jacketed heater (vibration dryer, etc.) is used under vacuum. Therefore, the same problem as the manufacturing method described in Patent Document 4 is generated.

[0039] Therefore, the present inventors have studied a method for removing a complexing agent from an electrolyte precursor formed by a complexing agent and a solid electrolyte raw material, and found that by supplying an electrolyte precursor content in a heated air flow, the complexing agent can be removed from the electrolyte precursor contained in the electrolyte precursor content. If the complexing agent is removed from the electrolyte precursor by heating in a heated air flow, the deterioration of the solid electrolyte caused by the contact of the powder of the solid electrolyte with the wall surface of a jacketed heater (vibration dryer, etc.) that has become locally high temperature can be suppressed.

[0040] In addition, since the heating is performed by using a heated airflow, it can be expected that as long as the supply amount of the heated airflow, especially the flow rate, is maintained within a certain range, the complexing agent can be removed from the electrolyte precursor-containing material regardless of the scale. Therefore, it also has the advantage of being easy to cope with large-scale equipment.

[0041] Based on the above findings, it was found that in a method for producing a sulfide solid electrolyte based on a liquid phase method (inhomogeneous method) in which a complexing agent is reacted with a solid electrolyte raw material, the complexing agent is removed from the powder of the electrolyte precursor by heating in a heated gas flow, thereby efficiently obtaining a sulfide solid electrolyte with high ion conductivity while adopting a liquid phase method, and mass production becomes easy.

[0042] (Various Aspects of the Present Embodiment)

[0043] The method for producing a sulfide solid electrolyte according to the first aspect of the present embodiment is as follows:

[0044] A method for manufacturing a sulfide solid electrolyte, comprising:

[0045] Mixing a raw material containing lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms with a complexing agent to obtain an electrolyte precursor containing material; and

[0046] Then heating is carried out in a heated air flow.

[0047] In the method for producing a sulfide solid electrolyte of the present embodiment, the electrolyte precursor containing material obtained by mixing a solid electrolyte raw material with a complexing agent may contain a complexing agent and a solid electrolyte raw material that do not contribute to the formation of the electrolyte precursor, and a solvent together with the electrolyte precursor. In the method for producing a sulfide solid electrolyte of the present embodiment, the complexing agent can be removed from the electrolyte precursor by heating in a heated air flow. In addition, in the case where a complexing agent or a solvent that does not contribute to the formation of the electrolyte precursor and remains is contained, it is also possible to remove them.

[0048] The electrolyte precursor is a precursor of the sulfide solid electrolyte obtained by the manufacturing method of the present embodiment, and is a substance that can become a sulfide solid electrolyte by removing the complexing agent. Here, the complexing agent refers to a reagent for complexing, that is, a reagent that can form a complex, and refers to a compound that easily forms a complex with the solid electrolyte raw material contained in the raw material content. Therefore, the electrolyte precursor is obtained by mixing the raw material content with the complexing agent, so more specifically, it can be said that it is a complex formed by the solid electrolyte raw material via the complexing agent.

[0049] The manufacturing method of this embodiment includes: after obtaining the electrolyte precursor containing material, heating in a heated air flow. The heating can be performed after obtaining the electrolyte precursor containing material, and the heating object during heating is the electrolyte precursor containing material, and in the case of drying described later, it is the electrolyte precursor (hereinafter, the electrolyte precursor containing material and the electrolyte precursor are sometimes collectively referred to as "heating object").

[0050] When heating electrolyte precursor containing things and removing complexing agent from electrolyte precursor, the main point is to heat electrolyte precursor containing things, especially electrolyte precursor contained in electrolyte precursor containing things in heated air flow. It is believed that heated air flow has the functions of utilizing temperature (heat) and air flow to dry and utilizing air flow to disperse heating object and remove complexing agent. Through these functions, complexing agent can be efficiently removed from electrolyte precursor. Heating objects such as electrolyte precursor containing things are dispersed in heated air flow by direct contact with heated air flow, so the contact area of ​​electrolyte precursor and heated air flow becomes larger. Therefore, the complexing agent contained in electrolyte precursor can be efficiently heated. And then, by the air flow of heated air flow, complexing agent can be separated and removed rapidly. Furthermore, the regeneration of the complex between the substance obtained by removing the complexing agent from the electrolyte precursor and the complexing agent (hereinafter, also referred to as "regeneration of the complex") and the generation of impurities caused by the electrolyte precursor and the complexing agent (hereinafter, also referred to as "generation of impurities") are suppressed, thereby obtaining a sulfide solid electrolyte with less impurities, high quality and high ion conductivity.

[0051] A method for producing a sulfide solid electrolyte according to a second aspect of the present embodiment is, in the above-mentioned first aspect,

[0052] The method includes drying the electrolyte precursor content.

[0053] In the manufacturing method of the present embodiment, if it is considered to remove the complexing agent contained in the electrolyte precursor, it is very important to directly heat the electrolyte precursor in the heated air flow. As the pre-stage of heating in the heated air flow, by drying the electrolyte precursor containing material, the residual complexing agent and the solvent used as needed that are not helpful for the formation of the electrolyte precursor can be removed, so that the electrolyte precursor is separated as a powder and heated in the heated air flow. By drying, the complexing agent contained in the electrolyte precursor can be heated more directly, so the complexing agent can be separated and removed more efficiently.

[0054] As a result, regeneration of the complex and generation of impurities are suppressed, and a sulfide solid electrolyte with less impurities, high quality, and high ion conductivity can be easily obtained more efficiently.

[0055] On the other hand, it is obvious that in the heating under vacuum using the jacket type heater in the conventional method, heat is transferred only by the contact between the electrolyte precursor and the wall surface inside the heater, so the contact efficiency is poor and the heat conduction efficiency is low. Therefore, it can be said that according to the production method of this embodiment, it is easy to obtain a sulfide solid electrolyte more efficiently than the conventional method.

[0056] Like this, the main purpose of drying in the manufacture method of the present embodiment is to remove the residual complexing agent and the solvent used as required that are not helpful to the formation of the electrolyte precursor from the electrolyte precursor containing thing.Therefore, removing the complexing agent from the electrolyte precursor is not carried out by drying, but by the heating in the heated air flow.On the other hand, the residual complexing agent and the solvent used as required can be removed by the heating in the heated air flow.In addition, removing the complexing agent from the electrolyte precursor certainly can also heat the electrolyte precursor in the heated air flow to contain thing and carry out.

[0057] A method for producing a sulfide solid electrolyte according to a third aspect of the present embodiment is, in the first or second aspect,

[0058] The temperature of the heated air flow is 100° C. or higher and 180° C. or lower.

[0059] As described above, by the temperature (heat) of the heated airflow and the effect of the airflow, the complexing agent contained in the electrolyte precursor is separated from the electrolyte precursor and becomes easy to be removed. Here, by setting the temperature of the heated airflow to the above-mentioned temperature range, in particular, because the heating performed by the effect of the temperature (heat) of the heated airflow is promoted, it is easy to separate and remove the complexing agent from the electrolyte precursor. Furthermore, it is easy to discharge the separated gaseous complexing agent together with the heated airflow to the outside of the system, and the regeneration of the complex and the generation of impurities caused by the separated complexing agent are suppressed, so that it is easy to obtain a sulfide solid electrolyte with few impurities, high quality and high ionic conductivity.

[0060] A fourth method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to third methods described above,

[0061] The supply amount of the heated air flow is 0.1m 3 / minute over 500m 3 / min or less.

[0062] By using the heated air flow at a supply rate within the above range, the air flow effect of the heated air flow can be utilized to achieve more efficient dispersion of the heated object and separation and removal of the complexing agent. Therefore, the regeneration of the complex and the generation of impurities are suppressed, and a sulfide solid electrolyte with less impurities, high quality and high ion conductivity can be easily obtained more efficiently.

[0063] Furthermore, by suppressing the supply amount of the heated airflow within a certain amount range, it is also possible to more easily cope with mass production.

[0064] A fifth method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to fourth methods described above,

[0065] The flow rate of the heated air flow is greater than 5 m / s and less than 35 m / s.

[0066] As described above, by the temperature (heat) of the heated airflow and the effect of the airflow, the complexing agent contained in the electrolyte precursor is separated from the electrolyte precursor and becomes easy to be removed. Here, by setting the flow rate of the heated airflow to the above range, it is particularly possible to more efficiently promote the separation and removal of the complexing agent using the effect of the heated airflow. In addition, it is easy to discharge the separated gaseous complexing agent together with the heated airflow to the outside of the system, and the regeneration of the complex and the generation of impurities caused by the separated complexing agent are suppressed, so that it is easy to obtain a sulfide solid electrolyte with few impurities, high quality and high ionic conductivity.

[0067] A sixth method for producing a sulfide solid electrolyte according to the present embodiment is, in the first to fifth methods described above,

[0068] The heating in the heated air flow is performed for 0.1 second to 1 minute.

[0069] In the production method of this embodiment, the complexing agent contained in the electrolyte precursor can be efficiently removed by heating with a heated airflow. Therefore, heating with a heated airflow can be performed in a short time of 0.1 second to 1 minute.

[0070] A seventh method for producing a sulfide solid electrolyte according to the present embodiment is, in the second to sixth methods described above,

[0071] The drying is performed at 5° C. to 110° C. under normal pressure or reduced pressure.

[0072] As conditions for drying the electrolyte precursor-containing material, by setting the pressure condition from normal pressure to reduced pressure and the temperature condition to 5° C. to 110° C., the electrolyte precursor-containing material can be dried more efficiently to obtain an electrolyte precursor.

[0073] The method for producing a sulfide solid electrolyte according to an eighth aspect of the present embodiment is, in the second to seventh aspects, the method comprising:

[0074] After the heating is performed in the heated air flow, further heating is performed.

[0075] By heating the electrolyte precursor in the heated gas stream, the complexing agent is removed from the electrolyte precursor to obtain an amorphous sulfide solid electrolyte. In addition to heating in the heated gas stream, further heating can be performed to obtain a crystalline sulfide solid electrolyte.

[0076] In the production method of the present embodiment, an amorphous sulfide solid electrolyte or a crystalline sulfide solid electrolyte can be produced as needed.

[0077] A ninth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in the first to eighth aspects,

[0078] The complexing agent is a compound having an amino group,

[0079] A tenth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, wherein in the first to ninth aspects,

[0080] The complexing agent is a compound having at least two tertiary amino groups in the molecule.

[0081] In the manufacturing method of the present embodiment, as described above, the complexing agent is a solvent having the property of forming a complex with the solid electrolyte raw material contained in the raw material content. Regarding the complexing agent, as described later, the compound having a heteroatom easily has the property of forming a complex with the solid electrolyte raw material, and is a preferred compound as a complexing agent. Among them, if it is a compound having a nitrogen atom as a heteroatom and then having a nitrogen atom in the form of an amino group, it is not only easier to form a complex, but also easy to introduce halogen atoms that are difficult to introduce in the formation of the complex, and it is easy to uniformly maintain the dispersed state of the solid electrolyte raw material. Therefore, it is easy to obtain higher ionic conductivity.

[0082] In addition, if a compound having an amino group is used as a complexing agent, in addition to the above properties, it also has the property of being easily separated from the electrolyte precursor and easily removed. As a result, the regeneration of the complex and the generation of impurities are suppressed, and a sulfide solid electrolyte with less impurities, high quality and high ion conductivity can be easily and efficiently obtained.

[0083] The eleventh method of producing a sulfide solid electrolyte according to the present embodiment is, in the first to tenth methods described above,

[0084] When heating is performed in the heated gas flow, no dielectric particles are used.

[0085] As described above, in the manufacturing method of this embodiment, it is important to heat the electrolyte precursor in the heated air flow, and preferably no dielectric particles are used. Excessive contact with the heated air flow caused by the adhesion of the electrolyte precursor to the dielectric particles can be suppressed, and the degradation of the amorphous sulfide solid electrolyte caused by the degradation of the electrolyte precursor can be suppressed, so that high ion conductivity can be easily obtained.

[0086] The heating in a heated gas flow in the production method of the present embodiment simply means heating with a heated gas flow, whereby the complexing agent can be efficiently removed from the electrolyte precursor, and a sulfide solid electrolyte having high ion conductivity can be efficiently produced.

[0087] A twelfth aspect of the present embodiment is a method for producing a sulfide solid electrolyte, in the above-mentioned first to eleventh aspects,

[0088] The sulfide solid electrolyte has a sulfide crystalline lithium superion conductor region type II crystal structure.

[0089] In the manufacturing method of this embodiment, by changing the type and blending ratio of the solid electrolyte raw material contained in the raw material content, a desired sulfide solid electrolyte can be manufactured. Sulfide solid electrolytes having a sulfide crystalline lithium superion conductor region II type crystal structure are known to be sulfide solid electrolytes with extremely high ion conductivity, and are preferably used as the sulfide solid electrolytes intended to be obtained by the manufacturing method of this embodiment.

[0090] (Solid Electrolyte)

[0091] In this specification, a "solid electrolyte" refers to an electrolyte that remains solid at 25° C. in a nitrogen atmosphere. The solid electrolyte in this embodiment contains lithium atoms, sulfur atoms, phosphorus atoms, and halogen atoms, and has ion conductivity due to lithium atoms.

[0092] The “solid electrolyte” includes both amorphous solid electrolytes and crystalline solid electrolytes.

[0093] In this specification, a crystalline solid electrolyte refers to a solid electrolyte in which a peak originating from a solid electrolyte is observed in an X-ray diffraction pattern in an X-ray diffraction measurement, and is a solid electrolyte that is independent of whether or not there is a peak originating from a raw material of the solid electrolyte. That is, the crystalline solid electrolyte includes a crystal structure originating from a solid electrolyte, and may be a part of it that is a crystal structure originating from the solid electrolyte, or may be a crystal structure originating from the solid electrolyte in its entirety. Furthermore, as long as the crystalline solid electrolyte has such an X-ray diffraction pattern as described above, an amorphous solid electrolyte may also be included in a part thereof. Therefore, the crystalline solid electrolyte includes a so-called glass ceramic obtained by heating an amorphous solid electrolyte to a temperature above the crystallization temperature.

[0094] In this specification, an amorphous solid electrolyte refers to an X-ray diffraction pattern having a halo pattern in which substantially no peaks other than peaks derived from the material are observed in X-ray diffraction measurement, regardless of the presence or absence of peaks derived from the raw materials of the solid electrolyte.

[0095] [Method for producing sulfide solid electrolyte]

[0096] The method for producing the sulfide solid electrolyte of this embodiment includes:

[0097] Mixing a raw material containing lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms with a complexing agent to obtain an electrolyte precursor containing material; and

[0098] Then heating is carried out in a heated air flow.

[0099] [Obtaining electrolyte precursor containing material]

[0100] The production method of the present embodiment includes mixing a raw material-containing material including lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms with a complexing agent to obtain an electrolyte precursor-containing material.

[0101] First, the production method of this embodiment will be described starting from the raw material contents.

[0102] (Ingredients contained in raw materials)

[0103] The raw material content used in this embodiment includes lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms, and more specifically, includes the following compounds (hereinafter also referred to as "solid electrolyte raw materials"): including one or more compounds selected from the group consisting of these atoms. The raw material content used in this embodiment preferably contains two or more solid electrolyte raw materials.

[0104] Representative examples of the solid electrolyte raw materials included in the raw material content include: lithium sulfide; lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide; phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); various phosphorus fluorides (PF3, PF5), various phosphorus chlorides (PCl3, PCl5, P2Cl4), various phosphorus bromides (PBr3, PBr5), various phosphorus iodides (PI3, P2I4), and the like; Phosphoryl halides such as phosphoryl fluoride (PSF3), thiophosphoryl chloride (PSCl3), thiophosphoryl bromide (PSBr3), thiophosphoryl iodide (PSI3), dichlorothiophosphoryl fluoride (PSCl2F), and dibromothiophosphoryl fluoride (PSBr2F); and other raw materials composed of at least two atoms selected from the above four atoms, halogen monomers such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2), preferably bromine (Br2) and iodine (I2).

[0105] As raw materials that can be used as solid electrolyte raw materials other than the above, for example, solid electrolyte raw materials containing at least one atom selected from the above four atoms and atoms other than the four atoms, more specifically, there can be mentioned: lithium compounds such as lithium oxide, lithium hydroxide, and lithium carbonate; alkali metal sulfides such as sodium sulfide, potassium sulfide, rubidium sulfide, and cesium sulfide; metal sulfides such as silicon sulfide, germanium sulfide, boron sulfide, gallium sulfide, tin sulfide (SnS, SnS2), aluminum sulfide, and zinc sulfide; phosphoric acid compounds such as sodium phosphate and lithium phosphate; alkali metal halides other than lithium such as sodium iodide, sodium fluoride, sodium chloride, and sodium bromide; metal halides such as aluminum halides, silicon halides, germanium halides, arsenic halides, selenium halides, tin halides, antimony halides, tellurium halides, and bismuth halides; halogenated phosphorus oxides such as phosphorus oxychloride (POCl3) and phosphorus oxybromide (POBr3); etc.

[0106] Preferred among the above are: lithium sulfide; phosphorus sulfides such as phosphorus trisulfide (P2S3) and phosphorus pentasulfide (P2S5); halogen monomers such as fluorine (F2), chlorine (Cl2), bromine (Br2), and iodine (I2); lithium halides such as lithium fluoride, lithium chloride, lithium bromide, and lithium iodide. In addition, when oxygen atoms are introduced into the solid electrolyte, lithium oxide, lithium hydroxide, and phosphate compounds such as lithium phosphate are preferred. As a combination of solid electrolyte raw materials, for example, a combination of lithium sulfide, phosphorus pentasulfide and lithium halide, a combination of lithium sulfide, phosphorus pentasulfide and halogen monomers can be preferably exemplified, preferably lithium bromide and lithium iodide as lithium halide, and preferably bromine and iodine as halogen monomers.

[0107] In this embodiment, Li3PS4 including a PS4 structure can also be used as a part of the raw material. Specifically, Li3PS4 and the like are prepared first and used as the raw material.

[0108] The content of Li3PS4 relative to the total of the raw materials is preferably 60 to 100 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 80 mol%.

[0109] In addition, when Li3PS4 and a halogen monomer are used, the content of the halogen monomer relative to Li3PS4 is preferably 1 to 50 mol%, more preferably 10 to 40 mol%, further preferably 20 to 30 mol%, and further preferably 22 to 28 mol%.

[0110] The lithium sulfide used in the present embodiment is preferably in the form of particles.

[0111] The average particle size of lithium sulfide particles (D 50 ) is preferably 0.1 μm to 1000 μm, more preferably 0.5 μm to 100 μm, and even more preferably 1 μm to 20 μm. In this specification, the average particle size (D 50 ) is the particle size when the particle size distribution cumulative curve is drawn from the smallest particle size to 50% (volume basis) of the whole, and the volume distribution is, for example, the average particle size that can be measured using a laser diffraction / scattering particle size distribution measuring device. In addition, among the raw materials exemplified as the above raw materials, the solid raw material preferably has an average particle size of the same degree as the above lithium sulfide particles, that is, the average particle size is preferably within the same range as the average particle size of the above lithium sulfide particles.

[0112] When lithium sulfide, phosphorus pentasulfide and lithium halide are used as solid electrolyte raw materials, from the viewpoint of obtaining higher chemical stability and higher ion conductivity, the ratio of lithium sulfide to the total of lithium sulfide and phosphorus pentasulfide is preferably 65 to 85 mol%, more preferably 70 to 82 mol%, and further preferably 74 to 80 mol%.

[0113] When lithium sulfide, phosphorus pentasulfide, lithium halide and other solid electrolyte raw materials used as needed are used, the content of lithium sulfide and phosphorus pentasulfide relative to the total of these raw materials is preferably 50 to 99 mol%, more preferably 55 to 85 mol%, and further preferably 60 to 80 mol%.

[0114] In addition, when lithium bromide and lithium iodide are used in combination as the lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 80 mol%, further preferably 35 to 80 mol%, and particularly preferably 45 to 70 mol%.

[0115] In addition, when lithium bromide and lithium chloride are used in combination as lithium halide, from the viewpoint of improving ion conductivity, the ratio of lithium bromide to the total of lithium bromide and lithium chloride is preferably 1 to 99 mol%, more preferably 15 to 75 mol%, further preferably 25 to 60 mol%, and particularly preferably 35 to 45 mol%.

[0116] When a halogen monomer is used as a solid electrolyte raw material and lithium sulfide and phosphorus pentasulfide are used, the ratio of the number of moles of lithium sulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen monomer to the total number of moles of lithium sulfide and phosphorus pentasulfide obtained by removing the same number of moles of lithium sulfide as the number of moles of the halogen monomer is preferably in the range of 60 to 90%, more preferably in the range of 65 to 85%, further preferably in the range of 68 to 82%, further preferably in the range of 72 to 78%, and particularly preferably in the range of 73 to 77%. This is because these ratios can obtain higher ion conductivity.

[0117] Furthermore, from the same viewpoint, when lithium sulfide, phosphorus pentasulfide and a halogen monomer are used, the content of the halogen monomer relative to the total amount of lithium sulfide, phosphorus pentasulfide and the halogen monomer is preferably 1 to 50 mol%, more preferably 2 to 40 mol%, further preferably 3 to 25 mol%, and further preferably 3 to 15 mol%.

[0118] When lithium sulfide, phosphorus pentasulfide, a halogen monomer and a lithium halide are used, the content of the halogen monomer relative to the total amount of these (α mol%) and the content of the lithium halide relative to the total amount of these (β mol%) preferably satisfy the following formula (2), more preferably satisfy the following formula (3), further preferably satisfy the following formula (4), and further preferably satisfy the following formula (5).

[0119] 2≤2α+β≤100…(2)

[0120] 4≤2α+β≤80…(3)

[0121] 6≤2α+β≤50…(4)

[0122] 6≤2α+β≤30…(5)

[0123] When two halogens are used as monomers, if the number of moles of one halogen atom in the substance is set to A1, and the number of moles of the other halogen atom in the substance is set to A2, then A1:A2 is preferably 1 to 99:99 to 1, more preferably 10:90 to 90:10, further preferably 20:80 to 80:20, and further preferably 30:70 to 70:30.

[0124] When two halogen monomers are used and the two halogen monomers are bromine and iodine, if the number of moles of bromine is set to A1 and the number of moles of iodine is set to A2, then A1:A2 is preferably 1:99 to 99:1, more preferably 20:80 to 80:20, further preferably 35:65 to 80:20, and further preferably 45:55 to 70:30.

[0125] Furthermore, when the two halogen monomers are bromine and chlorine, if the number of moles of bromine is set to B1 and the number of moles of chlorine is set to B2, then B1:B2 is preferably 1:99 to 99:1, more preferably 15:85 to 75:25, further preferably 25:75 to 60:40, and further preferably 35:45 to 65:55.

[0126] (Complexing agent)

[0127] As described above, the complexing agent is a compound that easily forms a complex with the solid electrolyte raw material contained in the raw material content, for example, a compound that can form a complex with lithium sulfide, phosphorus pentasulfide, or Li3PS4 obtained when these are used, and a solid electrolyte raw material containing halogen atoms (hereinafter collectively referred to as "solid electrolyte raw materials, etc."), which are preferably used as solid electrolyte raw materials.

[0128] As the complexing agent, any complexing agent having the above-mentioned properties can be used without particular limitation, and in particular, preferably, compounds containing atoms having high affinity with lithium atoms, such as nitrogen atoms, oxygen atoms, chlorine atoms and other heteroatoms can be exemplified, and more preferably, compounds containing groups containing these heteroatoms can be exemplified. This is because these heteroatoms and groups containing these heteroatoms can coordinate (bond) with lithium.

[0129] It is believed that the heteroatoms present in the molecules of the complexing agent have a high affinity for lithium atoms and have the property of easily bonding with the solid electrolyte raw material and the like to form a complex (hereinafter also referred to as a "complex"). Therefore, it is believed that by mixing the above-mentioned solid electrolyte raw material with the complexing agent to form a complex, it is easy to uniformly maintain the dispersion state of the solid electrolyte raw material, especially the dispersion state of the halogen atoms, so that a sulfide solid electrolyte with high ion conductivity can be obtained.

[0130] Whether the complexing agent can form a complex with the solid electrolyte raw material or the like can be directly confirmed by, for example, measuring an infrared absorption spectrum by FT-IR analysis (diffuse reflectance method).

[0131] When tetramethylethylenediamine (hereinafter, also referred to as "TMEDA"), one of the preferred complexing agents, was used as a complexing agent and the powder obtained by stirring lithium iodide (LiI) and the complexing agent itself were analyzed by FT-IR analysis (diffuse reflectance method), particularly at 1000 to 1250 cm-1 The peaks derived from CN stretching vibrations at 100 nm are different from the spectrum of TMEDA itself. In addition, it is known that the LiI-TMEDA complex is formed by stirring and mixing TMEDA and lithium iodide (e.g., Aust. J. Chem., 1988, 41, especially 1925-34). Figure 2 etc.), it is not wrong to think that a LiI-TMEDA complex is formed.

[0132] In addition, for example, when a powder obtained by stirring a complexing agent (TMEDA) and Li3PS4 is analyzed by FT-IR analysis (diffuse reflection method) in the same manner as above, it can be confirmed that the complexing agent (TMEDA) and Li3PS4 have a chromatographic wavelength of 1000 to 1250 cm -1 The peak derived from CN stretching vibration at 470° is different from the spectrum of TMEDA itself, but it is also confirmed to be similar to the spectrum of LiI-TMEDA complex. Therefore, it can be considered that Li3PS4-TMEDA complex is formed.

[0133] In the production method of the present embodiment, the complex obtained by mixing the raw material content substance and the complexing agent is used as an electrolyte precursor, and the complexing agent is removed from the powder of the electrolyte precursor in a heated gas flow to produce a sulfide solid electrolyte.

[0134] Preferably, the complexing agent has at least two heteroatoms capable of coordination (bonding) in the molecule, and more preferably has at least two groups containing heteroatoms in the molecule. By having at least two groups containing heteroatoms in the molecule, solid electrolyte raw materials, etc. can be bonded via at least two heteroatoms in the molecule. In addition, among the heteroatoms, nitrogen atoms are preferred, and amino groups are preferred as groups containing nitrogen atoms. That is, amine compounds are preferred as complexing agents.

[0135] As an amine compound, as long as it has an amino group in the molecule, it can promote the formation of the complex, so there is no particular limitation, and a compound having at least two amino groups in the molecule is preferred. By having such a structure, solid electrolyte raw materials can be bonded via at least two nitrogen atoms in the molecule to form a complex.

[0136] Examples of such amine compounds include amine compounds such as aliphatic amines, alicyclic amines, heterocyclic amines and aromatic amines, and these amine compounds may be used alone or in combination of two or more.

[0137] More specifically, the aliphatic amines may be preferably and representatively exemplified: aliphatic primary diamines such as ethylenediamine, diaminopropane, and diaminobutane; aliphatic secondary diamines such as N,N'-dimethylethylenediamine, N,N'-diethylethylenediamine, N,N'-dimethyldiaminopropane, and N,N'-diethyldiaminopropane; aliphatic tertiary diamines such as N,N,N',N'-tetramethyldiaminomethane, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetramethyldiaminopropane, N,N,N',N'-tetraethyldiaminopropane, N,N,N',N'-tetramethyldiaminobutane, N,N,N',N'-tetramethyldiaminopentane, and N,N,N',N'-tetramethyldiaminohexane; and the like. Here, in the examples of this specification, for example, if diaminobutane is used, unless otherwise specified, all isomers such as linear and branched isomers of butane are included in addition to isomers related to the position of the amino group such as 1,2-diaminobutane, 1,3-diaminobutane, and 1,4-diaminobutane.

[0138] The carbon number of the aliphatic amine is preferably 2 or more, more preferably 4 or more, and further preferably 6 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and further preferably 7 or less. In addition, the carbon number of the aliphatic hydrocarbon group in the aliphatic amine is preferably 2 or more, and the upper limit is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0139] The alicyclic amines may be preferably and representatively exemplified as primary alicyclic diamines such as cyclopropylene diamine and cyclohexyl diamine; secondary alicyclic diamines such as bisaminomethyl cyclohexane; tertiary alicyclic diamines such as N,N,N',N'-tetramethyl-cyclohexyl diamine and bis(ethylmethylamino)cyclohexane; and the like. Furthermore, the heterocyclic amines may be preferably and representatively exemplified as primary heterocyclic diamines such as isophorone diamine; secondary heterocyclic diamines such as piperazine and dipiperidyl propane; tertiary heterocyclic diamines such as N,N-dimethylpiperazine and bismethylpiperidyl propane; and the like.

[0140] The carbon number of the alicyclic amine or heterocyclic amine is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0141] In addition, as the aromatic amine, representative and preferred examples include: aromatic primary diamines such as phenylenediamine, toluenediamine, and naphthalenediamine; aromatic secondary diamines such as N-methylphenylenediamine, N,N'-dimethylphenylenediamine, N,N'-dimethylnaphthalenediamine, and N-naphthylethylenediamine; aromatic tertiary diamines such as N,N-dimethylphenylenediamine, N,N,N',N'-tetramethylphenylenediamine, N,N,N',N'-tetramethyldiaminodiphenylmethane, and N,N,N',N'-tetramethylnaphthalenediamine; and other aromatic diamines.

[0142] The number of carbon atoms in the aromatic amine is preferably 6 or more, more preferably 7 or more, and even more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and even more preferably 12 or less.

[0143] The amine compound used in the present embodiment may be an amine compound substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxy group, a hydroxyl group, a cyano group, or a halogen atom.

[0144] In addition, although diamines are illustrated as specific examples, the amine compounds that can be used in the present embodiment are obviously not limited to diamines. For example, trimethylamine, triethylamine, ethyldimethylamine, aliphatic monoamines corresponding to various diamines such as the above-mentioned aliphatic diamines; piperidine compounds such as piperidine, methylpiperidine, and tetramethylpiperidine; pyridine compounds such as pyridine and methylpyridine; morpholine compounds such as morpholine, methylmorpholine, and thiomorpholine; imidazole compounds such as imidazole and methylimidazole; and cyclopentadiene compounds corresponding to the above-mentioned alicyclic diamines. In addition, alicyclic monoamines such as monoamine; heterocyclic monoamines corresponding to the above-mentioned heterocyclic diamines; aromatic monoamines corresponding to the above-mentioned aromatic diamines, etc., can also be used. For example, polyamines having three or more amino groups such as diethylenetriamine, N,N',N"-trimethyldiethylenetriamine, N,N,N',N",N"-pentamethyldiethylenetriamine, triethylenetetramine, N,N'-bis[(dimethylamino)ethyl]-N,N'-dimethylethylenediamine, hexamethylenetetramine, tetraethylenepentamine, etc. can also be used.

[0145] Among the above, from the viewpoint of obtaining higher ion conductivity, a tertiary amine having a tertiary amino group as an amino group is preferred, a tertiary diamine having two tertiary amino groups is more preferred, a tertiary diamine having two tertiary amino groups at both terminals is further preferred, and an aliphatic tertiary diamine having tertiary amino groups at both terminals is further preferred. Among the above amine compounds, as the aliphatic tertiary diamine having tertiary amino groups at both terminals, tetramethylethylenediamine, tetraethylethylenediamine, tetramethyldiaminopropane, and tetraethyldiaminopropane are preferred. In consideration of availability, tetramethylethylenediamine and tetramethyldiaminopropane are preferred.

[0146] In addition, the same effects can be obtained by using a compound having a group other than an amino group containing a nitrogen atom as a hetero atom, for example, a compound having a nitro group, an amide group or the like.

[0147] In the production method of the present embodiment, as the complexing agent, in addition to the compound containing the above-mentioned nitrogen atom as a heteroatom, a compound containing an oxygen atom is also preferred.

[0148] As the compound containing an oxygen atom, a compound having one or more functional groups selected from an ether group and an ester group as a group containing an oxygen atom is preferred, and a compound having an ether group is particularly preferred. That is, as the complexing agent containing an oxygen atom, an ether compound is particularly preferred.

[0149] Examples of the ether compound include ether compounds such as aliphatic ether, alicyclic ether, heterocyclic ether and aromatic ether, and these ether compounds may be used alone or in combination of two or more.

[0150] More specifically, the aliphatic ethers include monoethers such as dimethyl ether, diethyl ether, diisopropyl ether, dibutyl ether, and tert-butyl methyl ether; diethers such as dimethoxymethane, dimethoxyethane, diethoxymethane, and diethoxyethane; polyethers having three or more ether groups such as diethylene glycol dimethyl ether (diglyme) and triethylene glycol dimethyl ether (triglyme); and ethers containing hydroxyl groups such as diethylene glycol and triethylene glycol.

[0151] The carbon number of the aliphatic ether is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and even more preferably 6 or less.

[0152] The carbon number of the aliphatic hydrocarbon group in the aliphatic ether is preferably 1 or more, and the upper limit is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0153] Examples of the alicyclic ether include ethylene oxide, propylene oxide, tetrahydrofuran, tetrahydropyran, dimethoxytetrahydrofuran, cyclopentyl methyl ether, dioxane, dioxolane, and the like. Examples of the heterocyclic ether include furan, benzofuran, benzopyran, dioxine, dioxin, morpholine, methoxyindole, and hydroxymethyldimethoxypyridine.

[0154] The carbon number of the alicyclic ether or heterocyclic ether is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0155] Examples of the aromatic ether include methyl phenyl ether (anisole), ethyl phenyl ether, dibenzyl ether, diphenyl ether, benzyl phenyl ether and naphthyl ether.

[0156] The number of carbon atoms in the aromatic ether is preferably 7 or more, more preferably 8 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.

[0157] The ether compound used in the present embodiment may be an ether compound substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxy group, a hydroxyl group, a cyano group, or a halogen atom.

[0158] From the viewpoint of obtaining higher ion conductivity, among the above ether compounds, aliphatic ethers are preferred, and dimethoxyethane and tetrahydrofuran are more preferred.

[0159] Examples of the ester compound include ester compounds such as aliphatic esters, alicyclic esters, heterocyclic esters and aromatic esters, and these ester compounds may be used alone or in combination of two or more.

[0160] More specifically, the aliphatic esters include formic acid esters such as methyl formate, ethyl formate and triethyl formate; acetates such as methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate and isobutyl acetate; propionic acid esters such as methyl propionate, ethyl propionate, propyl propionate and butyl propionate; oxalic acid esters such as dimethyl oxalate and diethyl oxalate; malonic acid esters such as dimethyl malonate and diethyl malonate; and succinic acid esters such as dimethyl succinate and diethyl succinate.

[0161] The carbon number of the aliphatic ester is preferably 2 or more, more preferably 3 or more, and further preferably 4 or more, and the upper limit is preferably 10 or less, more preferably 8 or less, and further preferably 7 or less. In addition, the carbon number of the aliphatic hydrocarbon group in the aliphatic ester is preferably 1 or more, more preferably 2 or more, and the upper limit is preferably 6 or less, more preferably 4 or less, and further preferably 3 or less.

[0162] Examples of the alicyclic esters include methyl cyclohexanecarboxylate, ethyl cyclohexanecarboxylate, dimethyl cyclohexanedicarboxylate, dibutyl cyclohexenedicarboxylate, and dibutyl cyclohexenedicarboxylate. Examples of the heterocyclic esters include methyl pyridinecarboxylate, ethyl pyridinecarboxylate, propyl pyridinecarboxylate, methyl pyrimidinecarboxylate, ethyl pyrimidinecarboxylate, or lactones such as acetyl lactone, propiolactone, butyrolactone, and valerolactone.

[0163] The carbon number of the alicyclic ester or heterocyclic ester is preferably 3 or more, more preferably 4 or more, and the upper limit is preferably 16 or less, more preferably 14 or less.

[0164] Examples of the aromatic ester include benzoic acid esters such as methyl benzoate, ethyl benzoate, propyl benzoate, and butyl benzoate; phthalic acid esters such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, butyl benzyl phthalate, and dicyclohexyl phthalate; and trimellitic acid esters such as trimethyl trimellitic acid, triethyl trimellitic acid, tripropyl trimellitic acid, tributyl trimellitic acid, and trioctyl trimellitic acid.

[0165] The number of carbon atoms in the aromatic ester is preferably 8 or more, more preferably 9 or more, and the upper limit is preferably 16 or less, more preferably 14 or less, and further preferably 12 or less.

[0166] The ester compound used in the present embodiment may be an ester compound substituted with a substituent such as an alkyl group, an alkenyl group, an alkoxy group, a hydroxyl group, a cyano group, or a halogen atom.

[0167] From the viewpoint of obtaining higher ion conductivity, among the above ester compounds, aliphatic esters are preferred, acetates are more preferred, and ethyl acetate is particularly preferred.

[0168] Regarding the amount of complexing agent added, from the viewpoint of efficiently forming a complex, the molar ratio of the amount of complexing agent added to the total molar amount of lithium atoms contained in the raw material content is preferably 0.1 to 2.0, more preferably 0.5 to 1.5, further preferably 0.8 to 1.2, and most preferably 1.0.

[0169] (mix)

[0170] In the production method of the present embodiment, the above-mentioned solid electrolyte raw material and the complexing agent are mixed.

[0171] In the present embodiment, the form of the mixed solid electrolyte raw material and the complexing agent can be any one of solid and liquid, but usually the solid electrolyte raw material comprises a solid and the complexing agent is a liquid, so the solid electrolyte raw material is usually present in the form of the liquid complexing agent for mixing. In addition, when mixing raw materials and complexing agents, solvents can be further mixed as needed. Below, in the description about the mixing of raw materials and complexing agents, in the absence of special instructions, the complexing agent also includes a solvent used as needed.

[0172] The method of mixing the solid electrolyte raw material and the complexing agent is not particularly limited, as long as the solid electrolyte raw material and the complexing agent are put into a device capable of mixing the solid electrolyte raw material and the complexing agent and mixed. For example, if the solid electrolyte raw material is gradually added after the complexing agent is supplied to the tank and the stirring blade is operated, a good mixing state of the solid electrolyte raw material can be obtained, and the dispersibility of the raw material is improved, so it is preferred.

[0173] However, when a halogen monomer is used as a solid electrolyte raw material, the solid electrolyte raw material is sometimes not solid. Specifically, at normal temperature and pressure, fluorine and chlorine become gases, and bromine becomes liquid. In such a case, for example, when the solid electrolyte raw material is liquid, it can be supplied to the tank together with the complexing agent separately from other solid solid electrolyte raw materials. In addition, when the solid electrolyte raw material is gas, it can be supplied in a manner of blowing into a substance obtained by adding a solid solid electrolyte raw material to a complexing agent.

[0174] The manufacturing method of the present embodiment is characterized in that it includes mixing solid electrolyte raw materials and complexing agents. That is, the solid electrolyte raw materials are mixed with the complexing agent, and there is no need to crush them. Therefore, it is also possible to manufacture by not using a method in which a medium-type pulverizer such as a ball mill, a bead mill, etc. is usually referred to as a pulverizer for the purpose of crushing the solid electrolyte raw materials. In the manufacturing method of the present embodiment, it is only necessary to simply mix the solid electrolyte raw materials with the complexing agent, and the solid electrolyte raw materials and the complexing agent contained in the raw material content are mixed to form a complex, i.e., an electrolyte precursor. In addition, in order to shorten the mixing time for obtaining the complex or to perform micronization, the mixture of the raw material and the complexing agent can also be crushed by a pulverizer, but as described above, it is preferred not to use a pulverizer.

[0175] On the other hand, the electrolyte precursor may be pulverized by a pulverizer.

[0176] As a device for mixing the solid electrolyte raw material with the complexing agent, for example, a mechanical stirring mixer with stirring blades in a tank can be exemplified. The mechanical stirring mixer can exemplify a high-speed stirring type mixer, a double-arm type mixer, etc., and from the viewpoint of improving the uniformity of the solid electrolyte raw material in the mixture of the solid electrolyte raw material and the complexing agent and obtaining higher ionic conductivity, it is preferred to use a high-speed stirring type mixer. In addition, as a high-speed stirring type mixer, a vertical axis rotating type mixer, a horizontal axis rotating type mixer, etc. can be exemplified, and any type of mixer can also be used.

[0177] As the shape of the stirring blade used in the mechanical stirring mixer, anchor type, blade type, arm type, belt type, multi-stage blade type, two-arm type, bucket type, biaxial blade type, flat blade type, C-type blade type etc. can be exemplified, from the viewpoint of improving the uniformity of solid electrolyte raw materials, obtaining higher ionic conductivity, preferably use bucket type, flat blade type, C-type blade type. In addition, in the mechanical stirring mixer, preferably set the circulation line that returns to the inside of the mixer again after the stirring object is discharged to the outside of the mixer. Thus, the raw materials with heavier specific gravity such as lithium halides will not precipitate and will not be stirred by retention, and more uniform mixing can be carried out.

[0178] Although the location of the circulation line is not particularly limited, it is preferably located at a location where the liquid is discharged from the bottom of the mixer and returned to the upper part of the mixer. Thus, the solid electrolyte raw material that is easy to precipitate is easily stirred evenly with the convection of the circulation. Furthermore, the return port is preferably located below the liquid surface of the stirring object. Thus, it is possible to suppress liquid splashing and cause the stirring object to adhere to the wall surface inside the mixer.

[0179] The temperature conditions for mixing the solid electrolyte raw material and the complexing agent are not particularly limited, and are, for example, -30 to 100°C, preferably -10 to 50°C, and more preferably about room temperature (23°C) (for example, about room temperature ±5°C). In addition, the mixing time is about 0.1 to 150 hours, and from the viewpoint of more uniform mixing and obtaining higher ion conductivity, it is preferably 1 to 120 hours, more preferably 4 to 100 hours, and even more preferably 8 to 80 hours.

[0180] By mixing the solid electrolyte raw material with the complexing agent, a complex is formed by the above-mentioned solid electrolyte raw material and the complexing agent. More specifically, it can be considered that the complex is obtained by the action of the lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms contained in the solid electrolyte raw material and the complexing agent, and these atoms are bonded via the complexing agent and / or directly bonded to each other without the complexing agent. That is, in the manufacturing method of this embodiment, the complex obtained by mixing the solid electrolyte raw material with the complexing agent can also be said to be composed of the complexing agent, lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms.

[0181] The complex obtained in this embodiment is not a complex completely dissolved in a complexing agent as a liquid, but is generally solid, so a suspension in which the complex is suspended in a complexing agent and a solvent used as needed can be obtained. Therefore, the method for manufacturing a solid electrolyte in this embodiment is equivalent to a so-called inhomogeneous system in a liquid phase method.

[0182] (Solvent)

[0183] In the present embodiment, a solvent may be further added when the solid electrolyte raw material and the complexing agent are mixed.

[0184] When a complex as a solid is formed in a complexing agent as a liquid, if the complex is easily dissolved in the complexing agent, separation of components may sometimes occur. Therefore, by using a solvent that does not dissolve the complex, the elution of the components in the electrolyte precursor can be suppressed. In addition, by using a solvent to mix the solid electrolyte raw material and the complexing agent, the formation of the complex can be promoted, so that each main component is more widely present, and the dispersed state of the solid electrolyte raw material, especially the dispersed state of the halogen atoms, can be obtained. The electrolyte precursor remains uniform, so the result is easy to play the effect of obtaining high ionic conductivity.

[0185] The method for manufacturing the solid electrolyte of the present embodiment is a so-called inhomogeneous method, and the complex is preferably not completely dissolved and precipitated relative to the complexing agent as a liquid. By adding a solvent, the solubility of the complex can be adjusted. In particular, since halogen atoms are easily eluted from the complex, by adding a solvent, the elution of halogen atoms can be suppressed to obtain the desired complex. As a result, it is easy to obtain a sulfide solid electrolyte with high ionic conductivity through an electrolyte precursor in which components such as a solid electrolyte raw material, especially a solid electrolyte raw material containing halogen atoms, are uniformly dispersed.

[0186] As a solvent having such properties, a solvent having a solubility parameter of 10 or less can be preferably mentioned. In the present specification, the solubility parameter is described in various documents, such as "Chemical Handbook" (published in 2004, 5th revised edition, Maruzen Co., Ltd.), and is a value δ ((cal / cm 3 ) 1 / 2 ), also known as Hildebrand parameter, SP value.

[0187] [Number 1]

[0188]

[0189] (In mathematical formula (1), ΔH is the molar heat of vaporization, R is the gas constant, T is the temperature, and V is the molar volume.)

[0190] By using a solvent with a solubility parameter of less than 10, it can be set to be relatively difficult to dissolve compared with the above-mentioned complexing agent, such as raw materials containing halogen atoms such as halogen atoms, lithium halides, and components containing halogen atoms (for example, aggregates obtained by bonding lithium halides with complexing agents) of solid electrolyte raw materials, particularly halogen atoms, and the like. Therefore, it is particularly easy to fix halogen atoms in the complex, and halogen atoms are present in the obtained electrolyte precursor and then in the solid electrolyte in a good dispersed state, and it is easy to obtain a solid electrolyte with high ionic conductivity. That is, the solvent used in the present embodiment is preferably a property with an insoluble complex. From the same viewpoint, the solubility parameter of the solvent is preferably less than 9.5, more preferably less than 9.0, and further preferably less than 8.5.

[0191] As the solvent used in the present embodiment, more specifically, a wide range of solvents that have been used in the manufacture of solid electrolytes can be used, for example, hydrocarbon solvents such as aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, and aromatic hydrocarbon solvents; alcohol solvents, ester solvents, aldehyde solvents, ketone solvents, ether solvents with a carbon number of 4 or more on one side, solvents containing carbon atoms and heteroatoms, etc.; and among these, it is preferred to appropriately select and use solvents having a solubility parameter in the above range.

[0192] More specifically, examples include aliphatic hydrocarbon solvents such as hexane (7.3), pentane (7.0), 2-ethylhexane, heptane (7.4), octane (7.5), decane, undecane, dodecane, and tridecane; alicyclic hydrocarbon solvents such as cyclohexane (8.2) and methylcyclohexane; benzene, toluene (8.8), xylene (8.8), mesitylene, ethylbenzene (8.8), tert-butylbenzene, trifluoromethylbenzene, nitrobenzene, chlorobenzene (9.5), chlorotoluene (9.6), and chlorobenzene. (8.8), aromatic hydrocarbon solvents such as bromobenzene; alcohol solvents such as ethanol (12.7), butanol (11.4); aldehyde solvents such as formaldehyde, acetaldehyde (10.3), dimethylformamide (12.1); ketone solvents such as acetone (9.9), methyl ethyl ketone; ether solvents such as dibutyl ether, cyclopentyl methyl ether (8.4), tert-butyl methyl ether, anisole; solvents containing carbon atoms and heteroatoms such as acetonitrile (11.9), dimethyl sulfoxide, carbon disulfide, etc. In addition, the values ​​in parentheses in the above examples are SP values.

[0193] In addition, the above examples are only examples, and solvents having isomers may also include all isomers. In addition, if it is a solvent substituted by a halogen atom, an alicyclic hydrocarbon solvent, or an aromatic hydrocarbon solvent, it may also include a solvent substituted by an aliphatic group such as an alkyl group.

[0194] Among these solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, and ether solvents are preferred. From the viewpoint of obtaining high ion conductivity more stably, heptane, cyclohexane, toluene, ethylbenzene, diethyl ether, diisopropyl ether, dibutyl ether, dimethoxyethane, cyclopentyl methyl ether, tert-butyl methyl ether, and anisole are more preferred. Diethyl ether, diisopropyl ether, and dibutyl ether are further preferred. Diisopropyl ether and dibutyl ether are further preferred, and cyclohexane is particularly preferred. The solvent used in this embodiment is preferably the organic solvent exemplified above and is an organic solvent different from the above-mentioned complexing agent. In this embodiment, these solvents can be used alone or in combination.

[0195] 〔dry〕

[0196] The production method of this embodiment may include drying the electrolyte precursor-containing material after obtaining the electrolyte precursor-containing material.

[0197] When removing the complexing agent, the electrolyte precursor obtained by drying the electrolyte precursor-containing material is heated in a heated air flow. This allows the electrolyte precursor to be heated more directly, and thus the complexing agent can be separated and removed more efficiently.

[0198] Examples of the drying method include filtration using a glass filter, solid-liquid separation by decantation, and solid-liquid separation using a centrifuge. Specifically, in the solid-liquid separation, it is easy to transfer the suspension to a container, and after solid precipitation, remove the complexing agent and the solvent used as needed to form a supernatant by decantation or filter using a glass filter with a pore size of about 10 to 200 μm, preferably 20 to 150 μm.

[0199] In addition, it is also possible to use a dryer etc. to dry by heating. The drying of the electrolyte precursor containing material can be carried out under any pressure conditions under pressure, normal pressure and reduced pressure, preferably under normal pressure or under reduced pressure. In particular, if it is considered to dry at a lower temperature, it is preferably dried under reduced pressure, further under vacuum, using a vacuum pump etc.

[0200] The temperature condition for drying can be carried out at a temperature above the boiling point of the residual complexing agent or the solvent used as required. Since the specific temperature condition can be changed according to the type of complexing agent and solvent used, it is impossible to generalize, but it is preferably above 5°C, more preferably above 10°C, and further preferably above 15°C, and the upper limit is preferably below 110°C, more preferably below 85°C, and further preferably below 70°C.

[0201] In addition, as described above, the pressure condition is preferably set at normal pressure or reduced pressure. When set at reduced pressure, specifically, it is preferably below 85 kPa, more preferably below 80 kPa, and further preferably below 70 kPa. The lower limit may be vacuum (0 kPa). Considering the ease of adjusting the pressure, it is preferably above 1 kPa, more preferably above 2 kPa, and further preferably above 3 kPa.

[0202] In the production method of the present embodiment, when drying is performed, the drying may be performed while heating after the above-mentioned solid-liquid separation.

[0203] In addition, in the manufacturing method of the present embodiment, drying may be performed or not. That is, in the manufacturing method of the present embodiment, the heating object heated in the heated air flow may be an electrolyte precursor-containing substance or an electrolyte precursor obtained by drying. Moreover, as described above, since the electrolyte precursor can be heated more directly, the electrolyte precursor is preferably used as the heating object.

[0204] [Heating in heated air flow]

[0205] The manufacturing method of this embodiment includes:

[0206] After the electrolyte precursor content is obtained, it is heated in a heated gas flow.

[0207] The electrolyte precursor-containing material obtained in the process of obtaining the electrolyte precursor-containing material and the electrolyte precursor after the above-mentioned drying (hereinafter sometimes the electrolyte precursor-containing material and the electrolyte precursor are collectively referred to as "heating object") are heated in a heated air flow, thereby removing the complexing agent from the electrolyte precursor, that is, removing the complexing agent from the complex formed by the solid electrolyte raw material and the complexing agent, thereby obtaining a sulfide solid electrolyte.

[0208] More specifically, heating in a heated air flow can be performed by supplying the heated object to the air flow of the heated gas, and for example, a commercially available device can be used as an air flow dryer. An air flow dryer is a device that can heat the heated object by supplying the heated object to a pipe supplied with a heated air flow, and preferably a direct hot air type air flow dryer in which the heated air flow is in direct contact with the heated object.

[0209] As the air flow dryer, preferably, for example, Figure 1 An airflow dryer having a cylindrical container-shaped heating portion as shown (also referred to as a "cylindrical container-type airflow dryer"). If the heating portion is a cylindrical container, the cross-sectional area of ​​the flow path of the heated object and the heated airflow becomes larger. Therefore, even if the heated object adheres to and solidifies on the inner wall surface, and the adhesion and solidification reduce the cross-sectional area of ​​the flow path, the influence of flow turbulence and occlusion on the change can be suppressed. As a result, stable drying is easy. In addition, compared with other forms described later, it is suitable for large-scale processing, and it is easy to continue long-term operation and easy to perform visual inspection and open cleaning, so the maintainability is also excellent.

[0210] As an airflow dryer, it is preferred to use an airflow dryer with a structure that can heat the heated object while making the heated airflow swirl, such as an airflow dryer provided with a dispersion plate to make the heated airflow swirl in the above-mentioned pipeline, an airflow dryer in which at least a portion of the above-mentioned pipeline has a ring shape or a semicircular shape (also respectively referred to as "ring-shaped airflow dryer", "semicircular airflow dryer"), etc. If such a structure is adopted, the attachment of the electrolyte precursor to the inner wall can be suppressed, and the mass difference between the substance after removing the complexing agent from the electrolyte precursor and the electrolyte precursor with the complexing agent remaining therein can be utilized, and classification can be performed by centrifugal force, so that the complexing agent can be removed more efficiently. In addition, the airflow dryer can be further miniaturized, and space saving can also be achieved.

[0211] In addition, as an airflow dryer, for example, a vertical long tube that maintains the length required for heating is preferably exemplified, and a heated airflow is introduced from the bottom of the vertical long tube to heat the object to be heated while flowing in parallel with the object to be heated (also called a "vertical long tube airflow dryer"). If a vertical long tube airflow dryer is used, the flow direction of the object to be heated and the heated airflow can be limited to upward, so that changes in the flow rate, particle size and density of the object to be heated can be coped with, and drying can be easily and stably performed. In addition, due to the simple structure, even if the object to be heated is attached to the inner wall, it can be easily peeled off, so it becomes easy to cope with long-term operation. Furthermore, relative to the increase in processing volume and drying capacity, since it is a method of coping by extending the vertical dimension, the setting area can be suppressed to be smaller than other forms, and it also has advantages in equipment setting.

[0212] In a vertical long tube type air flow dryer, the diameters of the vertical long tube portions may be uniform, or may be different and partially have a wide or narrow portion in order to adjust the heating state of the heating object.

[0213] The above-mentioned airflow dryer is mainly suitable for the circulation system, but, for example, a container-type airflow dryer can also be used to perform intermittent airflow drying. For example, a heated airflow is introduced from the lower part of the container to heat the heating object. In this case, if a reduction portion on the nozzle is provided at the introduction portion of the heated airflow, the heated airflow is introduced by increasing the flow rate, and the heated object can be mixed and stirred while being heated, thereby improving the drying efficiency. In the case of an intermittent type, the form of the airflow dryer is not limited, and any airflow dryer can be used, for example, the above-mentioned cylindrical container-type airflow dryer can be used.

[0214] In the case of intermittent drying, the heating object of each batch, the amount of introduction of the heated airflow, the temperature, and the heating time can be set arbitrarily. Therefore, the operating conditions can be set arbitrarily according to the state of the heated object, the degree of removal of the complexing agent from the heated object (electrolyte precursor), etc. In addition, by monitoring the change in the concentration of the complexing agent contained in the heated airflow discharged from the pneumatic dryer, it is possible to make it easy to make such an operation adjustment as the determination of whether the drying can be terminated, so the operation controllability is excellent.

[0215] When heating is performed in a heated air flow, it is preferred not to use dielectric particles. By not using dielectric particles such as ceramic balls and zirconium oxide beads, excessive contact with the heated air flow caused by the adhesion of the electrolyte precursor to the dielectric particles can be suppressed, and degradation of the amorphous sulfide solid electrolyte caused by degradation of the electrolyte precursor can be suppressed. Therefore, ion conductivity is improved.

[0216] (heating air flow)

[0217] As the gas used to heat the gas flow, any gas can be used without particular limitation as long as it is a gas, and for example, various gases such as inert gases such as nitrogen and argon or air can be used. If cost is taken into consideration, nitrogen and air can be used, and if improvement of ion conductivity is taken into consideration, nitrogen is preferably used. These gases can be used alone or in combination of multiple gases.

[0218] Furthermore, from the viewpoint of suppressing the quality reduction of the sulfide solid electrolyte due to water contained in the gas, the dew point temperature of the gas is preferably -10°C or lower, more preferably -20°C or lower, and even more preferably -30°C or lower.

[0219] As for the temperature of the heated airflow, there is no particular limitation as long as it can be heated to a degree that the complexing agent can be removed from the electrolyte precursor. It can be changed according to the type of complexing agent, so it cannot be generalized. It is preferably above 100°C, more preferably above 105°C, and more preferably above 110°C. As the upper limit, it is preferably below 180°C, more preferably below 170°C, more preferably below 160°C, and further preferably below 155°C. Here, the temperature of the heated airflow is the supply temperature of the heated airflow, for example, when the above-mentioned airflow dryer is used, it is the supply temperature to the airflow dryer. If it is within the above range, the complexing agent can be removed more efficiently.

[0220] The temperature of the heated airflow decreases when heating the electrolyte precursor, so for example, when using the above-mentioned airflow dryer, the outlet temperature from the airflow dryer is lower than the supply temperature to the airflow dryer (the temperature of the heated airflow). The outlet temperature varies depending on the scale of the airflow dryer, etc., so it cannot be generalized, but is usually 3°C or more lower than the supply temperature, and can be 5°C or more, or 10°C or more lower.

[0221] In addition, since the time for heating in the heated air flow is short and the temperature of the heated air flow is generally not reached, the temperature of the electrolyte precursor is lower than the temperature of the heated air flow. The temperature of the electrolyte precursor based on the heating in the heated air flow is preferably 80°C or more as the temperature after heating in the heated air flow (that is, the temperature of the sulfide solid electrolyte after the complexing agent is removed from the electrolyte precursor) and is more preferably 90°C or more, and more preferably 100°C or more. The upper limit is preferably 130°C or less, more preferably 125°C or less, and more preferably 120°C or less.

[0222] The amount of heated air flow supplied is not particularly limited as long as it is supplied to a degree that the complexing agent can be removed from the electrolyte precursor. It can be changed according to the type of complexing agent, the scale of the air flow dryer used, etc., and therefore cannot be generalized. It is preferably 0.1 m 3 / minute or more, more preferably 0.3m 3 / minute or more, more preferably 0.5m 3 / minute or more, and the upper limit is preferably 500m 3 / minute or less, more preferably 475m / min 3 / min or less, more preferably 450m 3 Within the above range, the complexing agent can be removed more efficiently.

[0223] The amount of heated air flow supplied is not particularly limited as long as it is supplied to a degree that the complexing agent can be removed from the electrolyte precursor. It can be changed according to the type of complexing agent, the scale of the air flow dryer used, etc., and therefore cannot be generalized. However, the amount of electrolyte precursor supplied (g / min) / the amount of heated air flow supplied (m 3 / minute), preferably 1.0 g / m 3 More preferably 1.5 g / m 3 More preferably, 2.0 g / m 3 The upper limit is preferably 50.0 g / m 3 the following.

[0224] As the flow velocity of heated air flow, just do not have special restriction as long as can remove the degree of complexing agent from electrolyte precursor, supply, can change according to the scale of the type of complexing agent, the air flow dryer used etc., therefore can not generalize, be preferably more than 5m / s, more preferably more than 7.5m / s, further preferably more than 9m / s, as upper limit, be preferably below 35m / s, more preferably below 30m / s, further preferably below 25m / s.If within the above scope, then can remove complexing agent more efficiently.

[0225] As for the heating time of heating in heated air flow, just do not have special restriction as long as can remove the degree of complexing agent from electrolyte precursor, supply, can change according to the scale of the type of complexing agent, the air flow dryer used etc., therefore can not generalize, be preferably below 1 minute as the upper limit, more preferably below 50 seconds, further preferably below 40 seconds, further preferably below 15 seconds, particularly preferably below 5 seconds.In addition, as the lower limit, be usually more than 0.05 second, be preferably more than 0.1 second, more preferably more than 0.2 second.

[0226] Thus, the heating time in the heated gas flow becomes extremely short. Therefore, for example, the electrolyte precursor is not exposed to high temperature conditions for a long time, and thermal degradation can be suppressed, thereby obtaining a sulfide solid electrolyte with high ion conductivity.

[0227] (Content of complexing agent)

[0228] By heating in the heated gas flow, the complexing agent can be removed from the electrolyte precursor, and the electrolyte precursor becomes an amorphous sulfide solid electrolyte, but the complexing agent cannot be completely removed from the electrolyte precursor, and as a result, the complexing agent may remain in the amorphous sulfide solid electrolyte. In this case, the content of the complexing agent contained in the sulfide solid electrolyte is preferably 0% by mass, that is, the complexing agent is not contained at all, but from the viewpoint of efficiently obtaining a sulfide solid electrolyte with high ion conductivity, it is usually 50% by mass or less, and further 45% by mass or less, 35% by mass or less, 25% by mass or less, 15% by mass or less, 10% by mass or less, 5% by mass or less, and the lower limit is about 0.1% by mass or more.

[0229] In addition, similarly to the complexing agent, when a solvent is used, the solvent may remain. In this case, the content of the solvent is also in the same numerical range as the content of the complexing agent described above.

[0230] In this specification, the content of the complexing agent contained in the sulfide solid electrolyte and the solvent used as needed is measured using a gas chromatograph (GC) on a solution obtained by dissolving the powder obtained in the examples, etc. in a mixed solution of water and pentanol, and the complexing agent and the high-boiling point solvent are quantified using an absolute standard curve (GC standard curve method).

[0231] (Powder recovery)

[0232] The manufacturing method of this embodiment preferably includes: after heating in the above-mentioned heated air flow, recovering the powder obtained by the heating. The heating object is heated in the heated air flow to become a powder in which the complexing agent is removed from the electrolyte precursor, that is, a powder of an amorphous sulfide solid electrolyte. After the powder in which the complexing agent is removed from the electrolyte precursor (powder of an amorphous sulfide solid electrolyte) is heated in the heated air flow, it is suspended in the heated air flow. Therefore, in the manufacturing process, it is preferred to recover the powder suspended in the heated air flow and then perform the crystallization by heating described later.

[0233] From the viewpoint of efficient capture, it is preferred to use a bag filter in the recovery of the powder suspended in the heated airflow. The powder (powder of amorphous sulfide solid electrolyte) from which the complexing agent is removed from the electrolyte precursor after being heated in the heated airflow is supplied to the bag filter, so that the powder (powder of amorphous sulfide solid electrolyte) from which the complexing agent is removed from the electrolyte precursor can be recovered. For example, when an airflow dryer is used, the powder can be recovered by connecting a bag filter downstream of the airflow dryer.

[0234] As the filter used for the bag filter, there can be used without particular limitation, and examples thereof include filters made of raw materials such as polypropylene, nylon, acrylic acid, polyester, kapok, wool, heat-resistant nylon, polyamide-polyimide, PPS (polyphenylene sulfide), glass fiber, PTFE (polytetrafluoroethylene), etc., and filters with functions such as electrostatic filters can also be used. Among them, filters made of heat-resistant nylon, polyamide-polyimide, PPS (polyphenylene sulfide), glass fiber, PTFE (polytetrafluoroethylene) are preferred, filters made of heat-resistant nylon, PPS (polyphenylene sulfide), PTFE (polytetrafluoroethylene) are more preferred, and filters made of PTFE (polytetrafluoroethylene) are particularly preferred.

[0235] Furthermore, the bag filter may include a dust removal unit, and preferably, for example, a pulsating reverse pressure type unit or a pulse jet type unit can be mentioned, among which a pulse jet type unit is preferred.

[0236] In the pipeline from the exhaust port of the bag filter, an induced ventilator may be provided to forcibly exhaust the gas exhausted from the exhaust port. By exhausting the gas using the induced ventilator, the filtration in the bag filter is smoothly performed, and the slurry can be dried in a shorter time.

[0237] 〔heating〕

[0238] The manufacturing method of this embodiment may include: further heating after heating in the above-mentioned heated air flow. By heating in the above-mentioned heated air flow, an amorphous sulfide solid electrolyte is obtained from the electrolyte precursor. When a crystalline sulfide solid electrolyte is desired, the amorphous sulfide solid electrolyte can be converted into a crystalline sulfide solid electrolyte by further heating in addition to heating in the heated air flow (hereinafter also referred to as "post-heating").

[0239] In addition, in the amorphous sulfide solid electrolyte obtained by heating in the above-mentioned heated air flow, a complexing agent and a solvent used as needed may remain. By further performing post-heating, the content of the complexing agent and solvent remaining in the amorphous sulfide solid electrolyte is reduced, so the quality of the sulfide solid electrolyte is improved, and high ion conductivity is easily obtained. In addition, by heating in the above-mentioned heated air flow, sometimes an amorphous sulfide solid electrolyte is not formed, but remains in the state of an electrolyte precursor. In this case, by performing post-heating, the complexing agent can be removed from the electrolyte precursor, and a crystalline sulfide solid electrolyte can be obtained via an amorphous sulfide solid electrolyte.

[0240] The heating temperature of the post-heating is not particularly limited as long as it is a temperature higher than the temperature of the substance (i.e., sulfide solid electrolyte) obtained by removing the complexing agent from the electrolyte precursor by heating in the above-mentioned heated air flow. For example, the heating temperature may be determined according to the structure of the crystalline solid electrolyte obtained by heating the amorphous sulfide solid electrolyte obtained by removing the complexing agent from the electrolyte precursor. Here, "the temperature of the substance (i.e., sulfide solid electrolyte) obtained by removing the complexing agent from the electrolyte precursor by heating in the heated air flow" refers to the temperature of the sulfide solid electrolyte at the outlet of the air flow dryer, for example.

[0241] As the temperature of post-heating, more specifically, the amorphous solid electrolyte is subjected to differential thermal analysis (DTA) under the condition of a temperature increase of 10°C / min using a differential thermal analyzer (DTA device), and the temperature of the peak top of the exothermic peak observed on the lowest temperature side is preferably set to a range of 5°C or more, more preferably 10°C or more, and further preferably 20°C or more, and the upper limit is not particularly limited, but can be set to about 40°C or less. By setting it to such a temperature range, not only can a crystalline solid electrolyte be obtained more efficiently and reliably, but also the content of the residual complexing agent and the solvent used as needed in the sulfide solid electrolyte can be reduced, and by reducing the content of the electrolyte precursor, the purity of the sulfide solid electrolyte can also be improved.

[0242] The heating temperature for post-heating cannot be generally specified because it varies depending on the structure of the obtained crystalline solid electrolyte, but is generally preferably above 130°C, more preferably above 140°C, and further preferably above 150°C. There is no particular upper limit, but it is preferably below 300°C, more preferably below 280°C, and further preferably below 250°C.

[0243] The heating time of the post-heating is not particularly limited as long as it is a time for obtaining the desired crystalline solid electrolyte, for example, preferably more than 1 minute, more preferably more than 10 minutes, more preferably more than 30 minutes, and more preferably more than 1 hour. In addition, the upper limit of the heating time is not particularly limited, preferably less than 24 hours, more preferably less than 10 hours, more preferably less than 5 hours, and more preferably less than 3 hours.

[0244] The post-heating can be performed under normal pressure, but in order to lower the heating temperature, it can also be performed under a reduced pressure atmosphere or further under a vacuum atmosphere.

[0245] As a pressure condition, when heating is performed under a reduced pressure atmosphere, it is preferably 85 kPa or less, more preferably 80 kPa or less, and further preferably 70 kPa or less. The lower limit may be vacuum (0 kPa). If the ease of adjusting the pressure is considered, it is preferably 1 kPa or more, more preferably 2 kPa or more, and further preferably 3 kPa or more. If the pressure condition is within the above range, the heating condition can be mild, and the enlargement of the device can be suppressed.

[0246] In addition, post-heating is preferably performed in an inert gas atmosphere (for example, a nitrogen atmosphere or an argon atmosphere) because this can prevent the crystalline solid electrolyte from being degraded (for example, oxidized).

[0247] The post-heating method is not particularly limited, and examples thereof include methods using a hot plate, a vacuum heating device, an argon atmosphere furnace, a firing furnace, etc. In addition, in industry, a horizontal dryer or a horizontal vibrating fluidized dryer having a heating unit and a feeding mechanism can also be used, and the method can be selected according to the heating processing amount.

[0248] (Amorphous sulfide solid electrolyte)

[0249] The sulfide solid electrolyte obtained by the production method of this embodiment can be made into any of an amorphous sulfide solid electrolyte and a crystalline sulfide solid electrolyte as desired. That is, if post-heating is not performed, an amorphous sulfide solid electrolyte can be obtained, and if post-heating is performed, a crystalline sulfide solid electrolyte can be obtained.

[0250] As the amorphous sulfide solid electrolyte obtained by the manufacturing method of this embodiment, lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms are contained. As representative amorphous sulfide solid electrolytes, for example, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc. can be preferably cited; solid electrolytes containing other atoms such as oxygen atoms and silicon atoms, such as solid electrolytes such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI, etc. From the viewpoint of obtaining higher ionic conductivity, solid electrolytes composed of lithium sulfide, phosphorus sulfide and lithium halide such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr, etc. are preferred.

[0251] The types of atoms constituting the amorphous sulfide solid electrolyte can be confirmed by, for example, an ICP emission spectrometer.

[0252] When the amorphous sulfide solid electrolyte obtained by the manufacturing method of this embodiment has at least Li2S-P2S5, from the viewpoint of obtaining higher ion conductivity, the molar ratio of Li2S to P2S5 is preferably 65 to 85:15 to 35, more preferably 70 to 80:20 to 30, and further preferably 72 to 78:22 to 28.

[0253] For example, when the amorphous sulfide solid electrolyte obtained by the manufacturing method of this embodiment is Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and phosphorus pentasulfide is preferably 60 to 95 mol%, more preferably 65 to 90 mol%, and further preferably 70 to 85 mol%. In addition, the ratio of lithium bromide to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.

[0254] In the amorphous sulfide solid electrolyte obtained by the production method of the present embodiment, the blending ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms is preferably 1.0 to 1.8: 1.0 to 2.0: 0.1 to 0.8: 0.01 to 0.6, more preferably 1.1 to 1.7: 1.2 to 1.8: 0.2 to 0.6: 0.05 to 0.5, and further preferably 1.2 to 1.6: 1.3 to 1.7: 0.25 to 0.5: 0.08 to 0.4. In addition, when bromine and iodine are used in combination as halogen atoms, the blending ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms, bromine and iodine is preferably 1.0-1.8: 1.0-2.0: 0.1-0.8: 0.01-0.3: 0.01-0.3, more preferably 1.1-1.7: 1.2-1.8: 0.2-0.6: 0.02-0.25: 0.02-0.25, more preferably 1.2-1.6: 1.3-1.7: 0.25-0.5: 0.03-0.2: 0.03-0.2, and further preferably 1.35-1.45: 1.4-1.7: 0.3-0.45: 0.04-0.18: 0.04-0.18. By setting the mixing ratio (molar ratio) of lithium atoms, sulfur atoms, phosphorus atoms and halogen atoms within the above range, a solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure described later and having higher ion conductivity can be easily obtained.

[0255] The shape of the amorphous sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape.

[0256] The average particle size (D 50), for example, 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, and the upper limit is 5 μm or less, further 3.0 μm or less, 1.5 μm or less, 1.0 μm or less, 0.5 μm or less. In this way, the sulfide solid electrolyte obtained by the manufacturing method of this embodiment does not use a jacketed heater (vibration dryer, etc.) used in the past when removing the complexing agent, so the generation of secondary particles caused by the aggregation of primary particles is suppressed, so that the average particle size becomes a smaller particle size in the above range.

[0257] Therefore, in the production method of the present embodiment, the pulverization (microparticulation) process does not need to be performed.

[0258] (Crystalline sulfide solid electrolyte)

[0259] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment can be a so-called glass ceramic obtained by heating an amorphous sulfide solid electrolyte to a temperature higher than the crystallization temperature, and its crystal structure can be exemplified by Li3PS4 crystal structure, Li4P2S6 crystal structure, Li7PS6 crystal structure, Li7P3S 11 A crystal structure, a crystal structure having peaks near 2θ=20.2° and 23.6° (for example, Japanese Patent Application Laid-Open No. 2013-16423), and the like.

[0260] Another example is Li 4-x Ge 1-x P x The S4 type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148 (7) A742-746 (2001)), and Li 4-x Ge 1-x P x S4 type thio-LISICON Region II type crystal structure (see Solid State Ionics, 177 (2006), 2721-2725). From the perspective of obtaining higher ionic conductivity, the crystal structure of the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment is preferably a thio-LISICON Region II type crystal structure among the above. Here, "thio-LISICON Region II type crystal structure" means Li 4-x Ge 1-x P xS4-type sulfide crystalline lithium superion conductor region II (thio-LISICON Region II) crystal structure, and Li 4-x Ge 1-x P x Any crystal structure similar to the S4 type thio-LISICON Region II type.

[0261] The crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment may be a crystalline sulfide solid electrolyte containing the above-mentioned sulfide crystallized lithium superion conductor region type II crystal structure, or may be a crystalline sulfide solid electrolyte containing the sulfide crystallized lithium superion conductor region type II crystal structure as a main crystal. From the viewpoint of obtaining higher ionic conductivity, it is preferred that the sulfide crystallized lithium superion conductor region type II crystal structure be contained as a main crystal. In this specification, "containing as a main crystal" means that the proportion of the target crystal structure in the crystal structure is 80% or more, preferably 90% or more, and more preferably 95% or more. In addition, from the viewpoint of obtaining higher ionic conductivity, the crystalline sulfide solid electrolyte obtained by the manufacturing method of this embodiment preferably does not contain crystalline Li3PS4 (β-Li3PS4).

[0262] In the X-ray diffraction measurement using CuKα rays, the diffraction peaks of the Li3PS4 crystal structure appear, for example, at 2θ=17.5°, 18.3°, 26.1°, 27.3°, and 30.0°; the diffraction peaks of the Li4P2S6 crystal structure appear, for example, at 2θ=16.9°, 27.1°, and 32.5°; the diffraction peaks of the Li7PS6 crystal structure appear, for example, at 2θ=15.3°, 25.2°, 29.6°, and 31.0°; and the diffraction peaks of the Li7P3S 11 The diffraction peaks of the crystal structure appear near 2θ=17.8°, 18.5°, 19.7°, 21.8°, 23.7°, 25.9°, 29.6°, and 30.0°, for example. 4-x Ge 1-x P x The diffraction peaks of the S4-type sulfide crystalline lithium superion conductor region II (thio-LISICONRegion II) crystal structure appear near 2θ=20.1°, 23.9°, and 29.5°, which are similar to Li 4-x Ge 1-x P x The diffraction peaks of the S4 type thio-LISICON Region II-type crystal structure appear near 2θ=20.2° and 23.6°, for example. These peak positions may fluctuate within a range of ±0.5°.

[0263] It is also preferable to exemplify a crystalline sulfide solid electrolyte having the following crystal structure: a thiogermanate-type crystal structure having the structural framework of Li7PS6 described above and in which a part of P is replaced by Si.

[0264] As a compositional formula of the thiogermanate-type crystal structure, for example, a compositional formula of Li 7-x P 1-y Si y S6 and Li 7+x P 1- y Si y S6 (where x is from -0.6 to 0.6 and y is from 0.1 to 0.6) can be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is cubic or orthorhombic, preferably cubic, and in X-ray diffraction measurement using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0265] As a compositional formula of the thiogermanate-type crystal structure, a compositional formula of Li 7-x-2y PS 6-x-y Cl x (0.8 ≤ x ≤ 1.7, 0 < y ≤ -0.25x + 0.5) can also be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0266] In addition, as a compositional formula of the thiogermanate-type crystal structure, a compositional formula of Li 7-x PS 6-x Ha x (where Ha is Cl or Br and x is preferably from 0.2 to 1.8) can also be exemplified. The thiogermanate-type crystal structure represented by this compositional formula is preferably cubic, and in X-ray diffraction measurement using CuKα radiation, it mainly has peaks appearing at positions of 2θ = 15.5°, 18.0°, 25.0°, 30.0°, 31.4°, 45.3°, 47.0°, and 52.0°.

[0267] In addition, these peak positions can fluctuate within a range of ±0.5°.

[0268] (Content of complexing agent)

[0269] After the removal, further heating is performed, so that the content of the complexing agent contained in the crystalline sulfide solid electrolyte is reduced more than the content of the complexing agent contained in the amorphous sulfide solid electrolyte.

[0270] The content of the complexing agent contained in the crystalline sulfide solid electrolyte is preferably 0 mass%, that is, no complexing agent is contained at all, but from the viewpoint of efficiently obtaining a sulfide solid electrolyte with high ion conductivity, it is usually 10 mass% or less, further 8 mass% or less, 5 mass% or less, 3 mass% or less, 1 mass% or less, and the lower limit is about 0.01 mass% or more.

[0271] In addition, similarly to the complexing agent, when a solvent is used, the solvent may remain. In this case, the content of the solvent is also in the same numerical range as the content of the complexing agent described above.

[0272] The shape of the crystalline sulfide solid electrolyte is not particularly limited, and may be, for example, a particle shape.

[0273] The average particle size (D 50 ), for example, 0.01 μm or more, further 0.03 μm or more, 0.05 μm or more, 0.1 μm or more, and the upper limit is 5 μm or less, further 3.0 μm or less, 1.5 μm or less, 1.0 μm or less, 0.5 μm or less. In this way, the sulfide solid electrolyte obtained by the manufacturing method of this embodiment does not use a jacketed heater (vibration dryer, etc.) used in the past when removing the complexing agent, so the generation of secondary particles caused by the aggregation of primary particles is suppressed, so that the average particle size becomes a smaller particle size in the above range.

[0274] Therefore, in the production method of the present embodiment, the pulverization (microparticulation) process does not need to be performed.

[0275] The specific surface area of ​​the sulfide solid electrolyte obtained by the production method of this embodiment is usually 10 m 2 / g or more, and further 15m 2 / g or more, 20m 2 / g or more, 25m 2 There is no particular upper limit, for example, 50 m 2 In this specification, the specific surface area is a value measured by the BET method (gas adsorption method), and the gas used may be nitrogen (nitrogen method) or krypton (krypton method), and is appropriately selected according to the size of the specific surface area.

[0276] (use)

[0277] The sulfide solid electrolyte obtained by the production method of the present embodiment has high ion conductivity and excellent battery performance, and therefore is suitable for use in batteries.

[0278] The sulfide solid electrolyte of this embodiment can be used for the positive electrode layer, the negative electrode layer, or the electrolyte layer. In addition, each layer can be produced by a known method.

[0279] In addition, the battery preferably uses a current collector in addition to the positive electrode layer, the electrolyte layer and the negative electrode layer, and the current collector can use a known current collector. For example, a layer obtained by coating a substance that reacts with the solid electrolyte such as Au, Pt, Al, Ti or Cu can be used.

[0280] Example

[0281] Next, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples at all.

[0282] (Measurement of powder XRD diffraction)

[0283] Powder X-ray diffraction (XRD) measurements were performed as follows.

[0284] The powder of the sulfide solid electrolyte obtained in the examples and comparative examples was filled into a groove with a diameter of 20 mm and a depth of 0.2 mm and flattened with glass to prepare a sample. The sample was sealed with a kapton film for XRD and measured under the following conditions in a manner that it was not in contact with air.

[0285] Measuring device: D2 PHASER, manufactured by Bruker Corporation

[0286] Tube voltage: 30kV

[0287] Tube current: 10mA

[0288] X-ray wavelength: Cu-Kα ray

[0289] Optical system: Concentration method

[0290] Slit configuration: Sola slit 4°, divergence slit 1mm, Kβ filter (Ni plate)

[0291] Detector: Semiconductor detector

[0292] Measuring range: 2θ = 10-60 degrees

[0293] Step width, scanning speed: 0.05deg, 0.05deg / second

[0294] (Measurement of ionic conductivity)

[0295] In this example, the measurement of ion conductivity was performed as follows.

[0296] The crystalline solid electrolyte obtained in the examples and comparative examples was formed into a 10 mm diameter (cross-sectional area S: 0.785 cm 2 ), round particles with a height (L) of 0.1 to 0.3 cm are used to make a sample. The top and bottom of the sample are taken as electrode terminals, and the AC impedance method is used for measurement at 25°C (frequency range: 5 MHz to 0.5 Hz, amplitude: 10 mV) to obtain a Cole-Cole plot. Near the right end of the arc observed in the high-frequency side area, the real part Z'(Ω) at the point where -Z"(Ω) is the smallest is taken as the bulk resistance R(Ω) of the electrolyte, and the ionic conductivity σ(S / cm) is calculated according to the following formula.

[0297] R=ρ(L / S)

[0298] σ=1 / ρ

[0299] (Measurement of Content of Complexing Agent Contained in Sulfide Solid Electrolyte)

[0300] The content of the complexing agent contained in the sulfide solid electrolyte is measured using a gas chromatograph (GC). The measurement outline is as follows: The sulfide solid electrolyte powder decomposed by a mixture of water and pentanol (the content of pentanol in the mixture: 90 volume %) is measured by GC, and the complexing agent is quantified using an absolute standard curve.

[0301] First, accurately weigh 0.1g of sample and put it into a vial. Add 10ml of a mixture of water and pentanol to the vial to completely decompose and dissolve the sample. Add about 1.5ml of the dissolved sample to a GC vial, cover it with a lid and fix it with a crimper. Set the automatic sampler to the GC for measurement. As a standard curve, weigh 0.5g of the complexing agent used and make it constant to volume with 50ml of a mixture of water and pentanol (equivalent to 10000μg / ml). Dilute it and adjust it to 2500, 1000, 250, 25, 2.5μg / ml (standard solution) for GC measurement. According to the peak area and the concentration of the standard solution, a standard curve is prepared by the least squares method. Substitute the GC peak area value of the sample solution into the standard curve and calculate the concentration in the sample solution according to the following formula.

[0302] Complexing agent content in sulfide solid electrolyte powder (mass %) = [concentration obtained from the standard curve (μg / ml) × amount of water and amyl alcohol mixture used to dissolve the sample (10 ml)] ÷ sample amount (g)

[0303] (Preparation Example: Preparation of Electrolyte Precursor)

[0304] The electrolyte precursors used in Examples and Comparative Examples were prepared by the following method: Here, the amounts of solid electrolyte raw materials, complexing agents, etc. used were the same as the ratios described in the following methods and were set to the necessary amounts in each Example and Comparative Example.

[0305] In a 1-liter reaction tank with a stirring blade, 13.19 g of lithium sulfide, 21.26 g of phosphorus pentasulfide, 4.15 g of lithium bromide and 6.40 g of lithium iodide (total amount of solid electrolyte raw materials: 45 g) were introduced under a nitrogen atmosphere. 100 mL of tetramethylethylenediamine (TMEDA) as a complexing agent and 800 mL of cyclohexane as a solvent were added thereto, and the stirring blade was operated to perform mixing under stirring at 30° C. for 72 hours. 456 g of zirconium oxide balls (diameter: 0.5 mm φ) were placed in a bead mill capable of circulating operation ("LABSTAR Mini LMZ015 (trade name)", manufactured by Ashizawa Finetech Co., Ltd.) (bead filling rate relative to the grinding chamber: 80%), and the balls were circulated between the above-mentioned reaction tank and the grinding chamber under the conditions of pump flow rate: 550 mL / min, peripheral speed: 8 m / s, and mill jacket temperature: 20°C, and ground for 60 minutes to obtain a slurry of an electrolyte precursor (complex). Then, the obtained slurry was immediately dried at room temperature (23°C) under vacuum to obtain a powder of an electrolyte precursor (complex). The content of the complexing agent contained in the obtained powder of the electrolyte precursor (complex) was 55% by mass.

[0306] (Airflow Dryer)

[0307] The powder of the electrolyte precursor obtained in the above preparation example is heated in a heated air flow using a Figure 1 A schematic diagram of a device for heating a heated air stream used in heating a device having a structure shown in FIG. Figure 1 The device shown is a device mainly equipped with an airflow dryer (cylindrical container type airflow dryer) and a bag filter, and is equipped with a blower and a heater for supplying heated airflow, and a mixer for air conveying the heated object through gas. In addition, although not shown in the figure, a feeder (not shown) that can supply the heated object in the form of powder or slurry can also be provided.

[0308] exist Figure 1In the device shown, the electrolyte precursor (heating object) is air-transported to the lower part of the airflow dryer by gas, and the heated airflow after the gas is heated by the heater is supplied from the bottom of the airflow dryer. The heating object heated in the heated airflow in the airflow dryer becomes a powder (amorphous sulfide powder) from which the complexing agent is removed from the electrolyte precursor, and the heated airflow containing it is supplied to the downstream bag filter. Then, the powder (amorphous sulfide powder) from which the complexing agent is removed from the electrolyte precursor is recovered by the bag filter, and the heated airflow after the powder is recovered is directly exhausted as it is.

[0309] (Example 1)

[0310] In the air flow dryer, nitrogen heated to 115°C is used as the heating air flow at a speed of 1m 3 / minute to supply to the air flow dryer, then use a desktop feeder to supply 4.2g / minute, and use 10.5L / minute nitrogen to air-feed the obtained electrolyte precursor powder to the air flow dryer. Using an air flow dryer, the heating object (powder of the electrolyte precursor) is heated in a heated air flow, and the heated air flow discharged from the air flow dryer is supplied to a bag filter to recover the powder (amorphous sulfide solid electrolyte) contained in the heated air flow from which the complexing agent is removed from the electrolyte precursor. Continue for 50 minutes (i.e., the operating time is 50 minutes). The temperature of the heated air flow at the outlet of the air flow dryer is 109°C, and the temperature of the heated air flow at the inlet of the bag filter is 61°C. In addition, the content of the complexing agent contained in the recovered powder (amorphous sulfide solid electrolyte) is 43% by mass.

[0311] The powder (amorphous sulfide solid electrolyte) obtained by removing the complexing agent from the obtained electrolyte precursor was heated at 110° C. for 2 hours in a Schlenk tube and further heated at 160° C. for 2 hours (post-heating) to obtain a crystalline sulfide solid electrolyte.

[0312] (Examples 2 and 3)

[0313] The powder was recovered in the same manner as in Example 1, except that the temperature and supply amount of the heated air flow supplied to the air flow dryer, the operation time, and the supply amount of the electrolyte precursor powder were set to the values ​​shown in Table 1. The outlet temperature of the air flow dryer, the inlet temperature of the bag filter, and the content of the complexing agent contained in the recovered powder (amorphous sulfide solid electrolyte) are shown in Table 1.

[0314] The ionic conductivity of the crystalline sulfide solid electrolyte obtained in Example 3 was measured and found to be 4.0 (mS / cm). In addition, the powder XRD diffraction measurement was performed on the crystalline sulfide solid electrolyte obtained in Example 3. The X-ray diffraction spectrum is shown in Figure 2 and 3 .like Figure 2 and 3 As shown, crystallization peaks were detected mainly at 2θ=20.2° and 23.6° in the X-ray diffraction spectrum, confirming that it was a crystalline sulfide solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure.

[0315] (Examples 4 to 8)

[0316] The powder was recovered in the same manner as in Example 1, except that the temperature and supply amount of the heated air flow supplied to the air flow dryer, the operation time, and the supply amount of the electrolyte precursor powder were set to the values ​​shown in Table 1. The outlet temperature of the air flow dryer, the inlet temperature of the bag filter, and the content of the complexing agent contained in the recovered powder (amorphous sulfide solid electrolyte) are shown in Table 1.

[0317] In addition, powder XRD diffraction measurements were performed on the crystalline sulfide solid electrolytes obtained in Examples 4 to 8. The X-ray diffraction spectra are shown in Figure 3 .like Figure 3 As shown, crystallization peaks were detected mainly at 2θ=20.2° and 23.6° in the X-ray diffraction spectrum, confirming that it was a crystalline sulfide solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure.

[0318] [Table 1]

[0319] Table 1

[0320]

[0321] The results of the examples confirmed that heating in a heated airflow can reduce the content of the complexing agent at the outlet of the airflow dryer in a very short time, and can provide a high-quality sulfide solid electrolyte with less impurities and high ion conductivity.

[0322] In addition, it was confirmed that the higher the supply temperature of the heated air flow, the lower the content of the complexing agent at the outlet of the air flow dryer, and the greater the supply amount of the heated air flow relative to the electrolyte precursor, the lower the content of the complexing agent at the outlet of the air flow dryer. Based on this, the operating conditions can be adjusted according to the required performance of the sulfide solid electrolyte.

[0323] (Comparative Example 1)

[0324] Using a vibration dryer ("VH-10 (model)", manufactured by Chuo Kako Ki Co., Ltd.), 350 g of the powder of the electrolyte precursor obtained in the above preparation example was heated at 110°C for 7 hours under vacuum to prepare an amorphous sulfide solid electrolyte, and then heated at 170°C for 2 hours under vacuum to obtain a crystalline sulfide solid electrolyte. Powder XRD diffraction was measured for the obtained crystalline sulfide solid electrolyte. The X-ray diffraction spectrum is shown in Figure 4 .

[0325] (Comparative Example 2)

[0326] A crystalline sulfide solid electrolyte was obtained in the same manner as in Comparative Example 1 except that the amount of the electrolyte precursor powder was changed from 350 g to 550 g. The powder XRD diffraction of the obtained crystalline sulfide solid electrolyte was measured. The X-ray diffraction spectrum is shown in Figure 4 .

[0327] according to Figure 4 As a result, the crystalline sulfide solid electrolytes obtained in Comparative Examples 1 and 2 detected crystallization peaks at 2θ=20.2° and 23.6°, so it can be said that they are crystalline sulfide solid electrolytes with a type II crystal structure in the sulfide crystalline lithium superion conductor region. However, a crystallization peak caused by halogen atoms (lithium bromide) was detected at 2θ=28°, and there were many impurities and it could not be said to be a solid electrolyte of excellent quality. In addition, the ionic conductivity of the crystalline sulfide solid electrolyte of Comparative Example 1 was 3.7 (mS / cm), and it was determined that the ionic conductivity was reduced due to the large number of impurities. In addition, the crystalline sulfide solid electrolyte of Comparative Example 2 clearly showed that there were many impurities and low quality according to the X-ray diffraction spectrum, so the ionic conductivity was not measured.

[0328] In Comparative Example 2 in which the amount of the electrolyte precursor is large, there are many crystallization peaks at 2θ=28°, and therefore it was also confirmed that it is difficult to cope with mass production without heating in a heated gas flow as used in the production method of the present embodiment.

[0329] (Comparative Example 3)

[0330] Except that in Example 1, the slurry obtained in the preparation example was used, Figure 1 The device shown with the flow dryer and bag filter is replaced by Figure 5 A crystalline sulfide solid electrolyte was obtained in the same manner as in Example 1 except that the apparatus was provided with a fluidized bed dryer using medium particles and a bag filter as shown.

[0331] Here, the slurry is supplied in the following manner: the nitrogen supply temperature to the fluidized bed dryer is 147°C, and the supply amount is set to 2.4 m / s (cross-section of the fluidized bed of a medium (medium particles) with a diameter of 98 mm, flow rate at 147°C), so that the temperature of the fluid containing gas and powder extracted from the top of the fluidized bed dryer is 110°C. In addition, ceramic particles with a particle size of 2 mm are used as the medium particles, and the filling rate of the ceramic particles is set to 30% by volume relative to the volume of the fluidized bed dryer. After the operation of the fluidized bed dryer enters a stable state, drying is continued for 48 hours, and the powder recovered by the bag filter is heated at 110°C for 2 hours under vacuum, and then heated at 180°C for 2 hours under vacuum to obtain a crystalline solid electrolyte. Powder XRD diffraction measurement is performed on the obtained crystalline sulfide solid electrolyte. The X-ray diffraction spectrum is shown in Figure 6 .also, Figure 6 The X-ray diffraction spectra of Examples 3 and 6 are also recorded for comparative reference.

[0332] (Examples 9 to 15)

[0333] The powder was recovered in the same manner as in Example 1, except that the temperature and supply amount of the heated air flow supplied to the air flow dryer, the operation time, and the supply amount of the electrolyte precursor powder were set to the values ​​shown in Table 2. The outlet temperature of the air flow dryer, the inlet temperature of the bag filter, and the content of the complexing agent contained in the recovered powder (amorphous sulfide solid electrolyte) are shown in Table 2.

[0334] In addition, powder XRD diffraction measurements were performed on the crystalline sulfide solid electrolytes obtained in Examples 9 to 15. The X-ray diffraction spectra are shown in Figure 7 .like Figure 7 As shown, crystallization peaks were detected mainly at 2θ=20.2° and 23.6° in the X-ray diffraction spectrum, confirming that it was a crystalline sulfide solid electrolyte having a sulfide crystalline lithium superion conductor region type II crystal structure.

[0335] [Table 2]

[0336] Table 2

[0337]

[0338] Examples 9 to 15 are examples in which the supply amount of the electrolyte precursor is increased compared to Examples 1 to 8. The results of Examples 9 to 15 confirm that even if the scale is increased, by maintaining the supply amount of the heated airflow, especially the flow rate, within a certain range while heating in the heated airflow, the content of the complexing agent at the outlet of the airflow dryer can be reduced in a very short time, and a high-quality sulfide solid electrolyte with less impurities and high ion conductivity can be obtained.

[0339] Industrial Applicability

[0340] According to the method for producing a sulfide solid electrolyte of the present embodiment, a sulfide solid electrolyte having high ion conductivity can be efficiently produced. In addition, since heating is performed using a heated airflow, as long as the supply amount, especially the flow rate, of the heated airflow is maintained within a certain range, the complexing agent can be removed from the electrolyte precursor-containing material regardless of the scale, so it can be easily handled.

[0341] The sulfide solid electrolyte of the present embodiment obtained by the production method of the present embodiment is suitable for use in batteries, particularly batteries used in information-related equipment or communication equipment such as personal computers, video cameras, and mobile phones.

Claims

1. A method for producing a sulfide solid electrolyte, characterized in that: include: Mixing a raw material containing lithium atoms, phosphorus atoms, sulfur atoms and halogen atoms with a complexing agent to obtain an electrolyte precursor containing material; as well as Then heating is carried out in a heated air flow.

2. The method for producing a sulfide solid electrolyte according to claim 1, wherein: The method includes drying the electrolyte precursor content.

3. The method for producing a sulfide solid electrolyte according to claim 1 or 2, wherein: The temperature of the heated air flow is 100° C. or higher and 180° C. or lower.

4. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 3, wherein: The supply amount of the heated air flow is 0.1m 3 / minute over 500m 3 / min or less.

5. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 4, wherein: The flow rate of the heated air flow is greater than 5 m / s and less than 35 m / s.

6. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 5, wherein: The heating in the heated air flow is performed for 0.1 second to 1 minute.

7. The method for producing a sulfide solid electrolyte according to any one of claims 2 to 6, wherein: The drying is performed at 5° C. to 110° C. under normal pressure or reduced pressure.

8. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 7, wherein: include: After the heating is performed in the heated air flow, further heating is performed.

9. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 8, wherein: The complexing agent is a compound having an amino group.

10. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 9, wherein: The complexing agent is a compound having at least two tertiary amino groups in the molecule.

11. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 10, wherein: When heating is performed in the heated gas flow, no dielectric particles are used.

12. The method for producing a sulfide solid electrolyte according to any one of claims 1 to 11, wherein: The sulfide solid electrolyte has a sulfide crystalline lithium superion conductor region type II crystal structure.

Citation Information

Patent Citations

  • Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material

    JP2013016423A

  • Liquid solution for formation of a solid electrolyte-containing layer of all-solid type lithium secondary battery, all-solid type lithium secondary battery, and method for manufacturing the same

    JP2014191899A

  • Production method of solid electrolyte

    WO2014192309A1

  • Solid lithium electrolytes and process of production

    WO2018054709A1

  • Method for producing solid electrolyte, and electrolyte precursor

    WO2020105737A1